Synthesis, Characterization and Antibacterial Activity of DEAE-C Loaded Cefixime Nano-Particles Against Resistant Bacterial Strains - Muhammad Tayyub Kazam; Saman Arooj; Mahpara Tabassum; Hamid Saeed; Mehwish Iqtedar; Nadeem Ahmad; Muhammad Islam; Muhammad Fawad Rasool; Muhammad Usama; Aleena Maryam (Journal of Pharmaceutical Innovation, 2026)

Spatio-temporal distribution patterns and risk assessment of microplastics along a coastal beach in southern Bangladesh - Md. Shawon Hossain; Kowshik Das Karmaker; Mahfujur Rahman; Arnob Ghosh; Swachsa Rahman; Shamiha Shafinaz Shreya; Jarin Tasnim; Mahir Tajwar; Nusrat Jahan Shimu; Mahmud Al Noor Tushar; Mir Shariful Islam; Mohammad Abdul Momin Siddique; et al. (Marine Pollution Bulletin, 2026)

Pathogenic mechanisms of Aeromonas hydrophila and the protective role of probiotics in sustainable aquaculture - Gelana Urgesa Ayana; Mukhtar Muhammad Abdullateef; Gazahegn Wakjira Yadata; Rehan Manzoor; Sahr Lamin Sumana; Abate Melaku Gelata; Md Mohidul Islam (Archives of Microbiology, 2026)

Analyzing integrated knowledge, attitudes and practices for the adoption of blast-resistant wheat varieties in Bangladesh: A structural equation modeling approach - Nasima Akter; Hasneen Jahan; Md Abdullah Al Noman; Md Monirul Islam; M. Wakilur Rahman; Sadika Haque; Pawan Kumar Singh; Muhammad Rezaul Kabir; Nanda Dulal Kundu (Crop Protection, 2026)

Finite element-based investigation and explainable machine learning prediction of moment resistance of steel flush end-plate connections - Md. Ibrahim Kholil; Muhammad Harunur Rashid; Aziz Ahmed; Md. Waliul Islam (Next Research, 2026)

From biosynthesis to food market translation of pullulan: AI-assisted production, structure-property-function interplay, regulatory perspectives, and commercialization - Muhammad Wajid Ullah; Su Sun; Zainab Jamil; Omar Mohammad Atta; Lili Zhang; Maleeha Azhar; Hidayat Ullah; Faryal Taimour; Mazhar Ul-Islam; Sehrish Manan; Yimin Fan; Zhiguo Wang (Carbohydrate Polymers, 2026)

Prevalence and cow-level risk factors for mild and severe subclinical mastitis in intensive and extensive dairy systems in Bangladesh - Muhammad Aktaruzzaman; M. Ariful Islam; Solama Akter Shanta; Mst. Tahomina Akter; Muhammad Tofazzal Hossain; Md. Nazmul Islam; Md. Shaffiul Alam; A. K. M. Anisur Rahman (Veterinary Research Communications, 2026)

Exploring the Molecular Mechanism of Arbutin as a Potential Inhibitor Against Melanoma: Insights from Network Pharmacology, Molecular Docking, Dynamics Simulations, and DFT Analysis - Md Rashedul Islam; Ishtiaq Qadri; Muhammad Afzal; Misbahuddin Rafeeq; Abdullah Alfaifi; Khadijah Abdullah Alfaifi; Sami I. Alzarea; Ehab M. M. Ali; Imran Kazmi (Journal of Pharmaceutical Innovation, 2026)

Microbial fermentation of cereals: nutritional, techno-functional, and compositional transformations toward data-driven process optimization - Yufeng Lin; Emad Karrar; Shahidul Islam; Zhao Jin; Usman Muhammad; Minwei Xu (Critical Reviews in Food Science and Nutrition, 2026)

Demineralization-assisted porous carbon production from palm oil shell: Enhancing pore accessibility under low-severity conditions for sustainable applications - Arfiana; Era Restu Finalis; Ilhamsyah Noor; Fausiah; Ade Andini; Endro Wahju Tjahjono; Erbert Ferdy Destian; Dorit Bayu Islam Nuswantoro; Herson Bangun; Bagus Alif Firmandoko; Muhammad Dikdik Gumelar; Dita Adi Saputra; et al. (Chemosphere, 2026)

Nitrogen stabilizers and crop rotation affect chemical properties and relative abundance of nitrification and denitrification genes in boreal podzolic soils - Irfan Mushtaq; Svetlana Yurgel; Zia-ul Islam; Yeukai Katanda; Muhammad Nadeem; Raymond Thomas; Lakshman Galagedara; Mumtaz Cheema (Science of The Total Environment, 2026)

Corrigendum to “Airborne microplastics and toxic trace metals in Dhaka: Identification and characterization in the urban aerosol” [Next Research 10 (2026) 101937] - Nishat Tasnim; Irana Mahjabeen; Md Firoz Khan; Md. Anowar Hosen; Md. Mominul Islam; Muhammad Nurul Huda; Md Tanvir Ahmed Chowdhury (Next Research, 2026)

A Novel Green MIP-202/TOCNF Composite Aerogel for Rapid PFAS Adsorption: Performance, Kinetics, and Mechanistic Insights - Muhammad Hamza; Muhammad Waqas; Islam Elsayed; Gregory Schueneman; El Barbary Hassan (Journal of Environmental Chemical Engineering, 2026)

Maternal and early-life arsenic exposure and relative telomere length in children: Findings from the BiRCH cohort - Lydia Lichtiger; Shohreh F. Farzan; Tariqul Islam; Syed Emdadul Haque; Mohammad H. Shahriar; Golam Sarwar; Alauddin Ahmed; Chunyu Liu; Brandon L. Pierce; Farzana Jasmine; Muhammad G. Kibriya; Habibul Ahsan; et al. (Environmental Research, 2026)

Correction to: Assessing the Population Dynamics and Stock Status of the Orange Mud Crab Scylla Olivacea (Herbst, 1796) in Two Oceanic Coasts of Thailand - Md. Rashedul Islam; Sukree Hajisamae; Siriporn Pradit; Muhammad Abdur Rouf; Sofiyudin Maae; Husneya Rensep (Thalassas: An International Journal of Marine Sciences, 2026)

Genomic and phenotypic insights into the probiotic and antimicrobial potential of Bacillus amyloliquefaciens BCSIR-AJ strain from garlic chutney - Mohammed Ayaz; Md Murshed Hasan Sarkar; Mohammad Monerul Islam; Muhammad Irfanul Islam; Farjana Akter Koly; Md. Rakibul Hasan; Md Saddam Hossain; Saiful Islam (Archives of Microbiology, 2026)

Structural and physiological adaptations conferring herbivory resistance in wild olive (Olea europaea L. subsp. cuspidata) - Faakeha Islam; Syed Mohsan Raza Shah; Farooq Ahmad; Mansoor Hameed; Sana Basharat; Sana Fatima; Ansar Mehmood; Zahida Parveen; Ansa Asghar; Muhammad Sajid Aqeel Ahmad; Muhammad Ashraf; Khawaja Shafique Ahmad (Physiology and Molecular Biology of Plants, 2026)

Retraction Note: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2026)

Pesticides-induced histopathological and biochemical alterations in fish: Impacts and restoration strategies - Shariqul Islam; Muhammad Sohail; Md. Fazle Rohani; Shahadat Hossain; S.M. Majharul Islam (Science of The Total Environment, 2026)

Airborne microplastics and toxic trace metals in Dhaka: Identification and characterization in the urban aerosol - Nishat Tasnim; Irana Mahjabeen; Md Firoz Khan; Md. Anowar Hosen; Md. Mominul Islam; Muhammad Nurul Huda; Md Tanvir Ahmed Chowdhury (Next Research, 2026)

Interlinking behaviour, technology, and roles in women rice seed producer groups of Bangladesh - Swati Nayak; Muhammad Ashraful Habib; Subhasmita Mohapatra; Saidul Islam; Sk Mosharaf Hossain (Next Research, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Evaluating the effect of Iron biofortification on nutraceutical and aromatic profiles of cereal grains: A case study of pearl millet - Hamza M.A. Abaker; Sulafa B.H. Hashim; Haroon Elrasheid Tahir; Muhammad Arslan; Gustav Komla Mahunu; Zhuhai Li; Xiaodong Zhai; Abdalbasit Adam Mariod; Mohammad Rezaul Islam Shishir; Magdi Ali Osman Mohammed; Ahmed Gaafar Mohammed Elgorashi; Alaa K.M. Khogly; et al. (Food Chemistry, 2026)

Source-dependent effects of dietary astaxanthins on health and mucosal immunity in Atlantic salmon (Salmo salar) - S.M.Majharul Islam; Mette Sørensen; Gabriel Ossenkamp; Muhammad A.B. Siddik; Monica F. Brinchmann; Jørgen Lerfall; Viviane Verlhac-Trichet; Florence Perera Willora; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2026)

Invisible Dangers: A Risk Assessment of Cooking Biomass Fuels and Their Trace Element Exposure in Rural Bangladesh - Md. Badiuzzaman Khan; Muhammad Azizal Hoque; Mauro Masiol; Shamsunnahar Setu; Niger Sultana; M. Rafiqul Islam; Mahmud Hossain (Exposure and Health, 2026)

AI-Enabled Digitalization and Environmental Practices in Municipal Waste Management: Pathways to Climate Sustainability in Pakistan - Muhammad Ahsan Iqbal; Asifa Muhammad Sabir; Kundan Kumar; Md Mahfujul Islam (Environmental Management, 2026)
Rapid urbanization and the intensifying pressures of climate change have elevated solid waste management (SWM) as a critical public service challenge. Evidence on the joint mediating effects of digital transformation and environmental governance between municipal SWM and climate sustainability remains questionable. This study examines the role of SWM in promoting climate sustainability by evaluating environmental management practices and AI-enabled digitalization. Data were collected from 406 employees across seven Water and Sanitation Service Companies (WSSCs) in Khyber Pakhtunkhwa, Pakistan, using a cross-sectional survey with a structured and validated instrument. The analytical approach involved Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with bootstrapped mediation analysis (5000 resamples), executed in SPSS and AMOS software. The study measured waste management effectiveness, environmental practices, AI-enabled digital systems, and sustainability outcomes across economic–environmental–social nexus. Findings reveal a significant positive relationship between effective SWM and climate sustainability (β = 0.41, p < 0.001). Environmental practices including regulatory compliance, pollution control, and workforce training along with AI-driven digital capabilities including real-time tracking, route optimization, electronic service reporting, and data dashboards play a strong mediating role (indirect effects: ENV = 0.13; DIG = 0.12; joint = 0.21). The results suggest that municipal waste systems achieve greater climate benefits when routine operations are supported by integrated environmental management and smart digital technologies. The study contributes to the research on sustainable models, circular economy, and smart urban governance, offering policy guidance for municipal authorities in Pakistan, through AI-enabled tools and solutions, environmental governance practices, and SDG-aligned incentives.

Ecological and human health risks from railway-associated contaminants: a case study of trace metal and PAH pollution along a commuter line in Chittagong, Bangladesh - Mahbub Alam; Md. Samrat Mohay Menul Islam; Muhammad Abu Bakar; Md. Ashraful Islam; Suman Das; Sreebash Chandra Bhattacharjee; Kaiser Mahmood Fahim; Md. Hasan Mahmud Babu (Environmental Geochemistry and Health, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Harnessing the Potential of Nodule Endophytic Bacteria to Improve Soybean Growth Under Saline Conditions - Humaira Islam; Mohsin Tariq; Kashif Sattar; Tahira Yasmeen; Muhammad Abdul Rehman Rashid (Current Microbiology, 2026)

Harnessing phage biocontrol strategies for managing bacterial plant pathogens - Sajad Ali; Tarequl Islam; Mohammed A Almalki; Muhammad Fazle Rabbee (BioControl, 2026)

Red seaweed extract as a phycological biostimulant enhances groundnut drought tolerance: Integrated agronomic, physiological, and UAV-based insights - Malihatun Nesa; Sudip Sen; Md. Farhadur Rahman; Md. Moshiul Islam; S. M. Rafiquzzaman; Md. Main Uddin Miah; Abdul Kaium Tuhin; Hasan Muhammad Abdullah (Journal of Applied Phycology, 2026)

A forensic analysis of the Sitakunda BM depot chemical blast: Source apportionment, environmental health risks, and implications for chemical safety management - Md. Ripaj Uddin; AHM Shofiul Islam Molla Jamal; Md. Ahedul Akbor; Mohammad Moniruzzaman; Muhammad Abdullah Al Mansur; Nisat Taslum Jhumur; Md. Golam Mostafa (Next Research, 2026)

Sustainable development of novel lime marble dust composite compressed earth blocks: mechanical and durability performance evaluation - Salman Farooq; Zia Ul Islam; Muhammad Isa Khan; Hamza Sajjad (Innovative Infrastructure Solutions, 2026)

Mangrove Ecosystem Carbon Stocks: Insights from Setiu Lagoon, Malaysia - Mohammad Ahsanul Islam; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Md Masum Billah; AFM Arifur Rahman; Muhammad Shariefuddin Bin Mohd Sukeri; Md Khurshid Alam Bhuiyan (Estuaries and Coasts, 2026)

Distribution, source, and risk analysis of PAHs and trace elements in roadside soils of Dhaka-Bhanga expressway: a case study - S. M. Fazle Rabbi; Lamyea Rahman; Md. Samrat Mohay Menul Islam; Md. Ashraful Islam; Shariful Islam; Md. Mashfiqur Rahman Niloy; Muhammad Abu Bakar; Md. Rakibul Hasan; Md. Kamruzzaman (Environmental Monitoring and Assessment, 2026)

Assessment of groundwater quality and fluoride health risks using multimetric indices in Balochistan, Pakistan - Muhammad Zaheer; Waqar Azeem Jadoon; Memet Varol; Ibraheem Khan; Abu Reza Md Towfiqul Islam (Journal of Environmental Chemical Engineering, 2026)

Ambient ozone pollution degrades rice grain nutritional quality and straw feed value under field conditions in Bangladesh - Rigyan Gupta; Muhammad Shahedul Alam; Shamsul H. Prodhan; Kamrul Islam; Shamsun Nahar Begum; Md. Nurealam Siddiqui; Mirza Mofazzal Islam; Md Ashrafuzzaman (Environmental Pollution, 2026)

Synthesis and structure–activity relationship studies of 1,2,4-triazole–benzoxazepine hybrids as α-glucosidase inhibitors: molecular docking and biological evaluation - Muhammad Ashram; Ahmed Al-Mustafa; Almeqdad Y. Habashneh; Hamza I. Al-Hrerat; Mahmoud A. Al-Sha’er; Firas F. Awwadi; Islam Ashram (Medicinal Chemistry Research, 2026)

Spatiotemporal trends and urban-climate interactions of land surface temperature dynamics across Bangladesh - Md. Riyadul Haque; Arman; Muhammad Moniruzzaman; Sujit Kumar Roy; A.K.M. Saiful Islam (Anthropocene, 2026)

A review on the effects of iron (Fe) on Ulva prolifera: Mechanisms of growth promotion, inhibition, and biochemical responses - Md Mohidul Islam; Sahr Lamin Sumana; Mukhtar Abdullateef Muhammad; Gelena Urgesa Ayana; Shisi Fu; Abubakar Shuaibu; Ahmed E. Elshafey; Yifei Shen; Yuqing Sun; Md. Simul Bhuyan; Md. Enamul Hoq; Touhidul Hoque Shuvo; et al. (Algal Research, 2026)

Corrigendum to “Comparative population parameters and stock assessment of three symmetric Scylla species in coastal waters of the Gulf of Thailand” [Reg. Stud. Mar. Sci. 94 (2026) 1–12] - Md. Rashedul Islam; Sukree Hajisamae; Siriporn Pradit; Muhammad Abdur Rouf; Sofiyudin Maae; Husneya Rensep (Regional Studies in Marine Science, 2026)

Modeling ecosystem structure and trophic dynamics of northern Bay of Bengal, Bangladesh - Debashis Kumar Mondal; Halima Khatun; Kangshun Zhao; Muhammad Farooq; Md. Fakhrul Islam; Md. Abdul Halim; Sundaralingam Darsigan; Jun Xu (Regional Studies in Marine Science, 2026)

Carvacrol-enriched chitosan/berry wax active films via Pickering emulsion: a sustainable solution for extending meat shelf-life - Suliman Khan; Ke Zhang; Sulafa B.H. Hashim; Mohammad Rezaul Islam Shishir; Naymul Karim; Muhammad Bilal; Zhihua Li; Xiaodong Zhai; Xiaobo Zou; Fujun Li (Food Chemistry, 2026)

Recent Advances in p-Type Nickel Oxide (NiO) for Solar-Light-Driven Photocatalytic Degradation of Organic Pollutants - Mansoor sultan; Nisar Ali; Muhammad Naseem; Shah Ihsan; Mazharul islam; Abdul kareem; Shahbaz Khan; Bakht Muhammad Khan; Fawad khan; Farman Ali; Adnan Khan; Rayya Ahmed Al Balushi; et al. (Water, Air, & Soil Pollution, 2026)

Correction to: Sedative effects of physcion and its modulatory interaction with diazepam: in vivo and in silico evaluation - Md. Shadin; Md. Shimul Bhuia; Mohammed Alfaifi; Abdullah H. Altemani; Faisal H. Altemani; Faisal Alsenani; Raihan Chowdhury; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sedative effects of physcion and its modulatory interaction with diazepam: in vivo and in silico evaluation - Md. Shadin; Md. Shimul Bhuia; Mohammed Alfaifi; Abdullah H. Altemani; Faisal H. Altemani; Faisal Alsenani; Raihan Chowdhury; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Anxiolytic-like effects of p-coumaric acid via GABAergic interaction pathways: an in vivo and in silico study - Madhu Sah; Balaram Das; Ramesh Kumar Mandal; Raihan Chowdhury; Mohammad Y. Alshahrani; Muhammad Ali Khan; Anik Kumar Saha; U Ching Aoung Chak; Sadia Akhter; Md. Fazla Alahi Nikson; Shama Mohanta; H. M. Shadid Hossain Snigdha; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Improving RGB image recognition in the YOLO11n algorithm for accurate detection of tea plant diseases - Jinxian Tao; Xiaoli Li; Jingfei Zhang; Muhammad Shoaib; Muhammad Adnan Islam; Ibrar Ahmad; Yong He; Sitan Ye; Yujie Wang; Binhui Liao; Mostafa Gouda (Journal of Zhejiang University-SCIENCE B, 2026)

Heavy metal contamination in agricultural soils: an environmental and food safety perspective - Siraj ud Din; Muhammad Subhanullah; Bakht Rawan; Shahla Nazneen; Muhammad Ilyas; Thiago Machado da Silva Acioly; Waheed Ullah; Abdullah Faiz Al Asmari; Saiful Islam (Environmental Monitoring and Assessment, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

EEG-based cognitive state classification using a leakage-safe stacked ensemble learning approach - Md Rafiqul Islam; Riad Hasan; Md Abu Layek; Muhammad Aminur Rahaman (Next Research, 2026)

New frontiers in beverage fortification: Delivery of functional ingredients via micro- and nanoencapsulation in dairy and non-dairy beverages - Mohammad Rezaul Islam Shishir; Suliman Khan; Naymul Karim; Muhammad Bilal; Sarfaraz Hussain; Md Saifullah; Ahmed K. Rashwan; Haroon Elrasheid Tahir; Isam A. Mohamed Ahmed; Xinhua Zhang; Fujun Li (Food Research International, 2026)

Retraction notice to ‘In-house fabrication of macro-porous biopolymeric hydrogel and its deployment for adsorptive remediation of lead and cadmium from water matrices’ [Environ. Res. 214 (2022) 113790] - Muhammad Khalid Azeem; Muhammad Rizwan; Atif Islam; Atta Rasool; Shahzad Maqsood Khan; Rafi Ullah Khan; Tahir Rasheed; Muhammad Bilal; Hafiz M.N. Iqbal (Environmental Research, 2026)

Three Characterized Probiotics from Dairy Sources—Weissella confusa (ProY 5.1), Enterococcus lactis (ProY 5.3), and Leuconostoc lactis (RM 2.1)—Exhibit Potential for Antidiarrheal Effects - Jannatul Ferdous; Md. Saddam Hossain; Palash Kumar Sarker; Md. Shimul Bhuia; Md. Sakib Al Hasan; Raihan Chowdhury; Md. Sarafat Ali; Md. Robiul Auwal; Keshob Chandra Das; Muhammad Torequl Islam; Abu Hashem; Md. Salimullah (Probiotics and Antimicrobial Proteins, 2026)

Correction: Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat‑Ul‑Ain Raza (Environmental Geochemistry and Health, 2026)

Development and evaluation of climate-smart aquaculture interventions to enhance livelihood resilience in salt farming communities of Bangladesh - Md. Rakibul Hasan; Muhammad Meezanur Rahman; Seikh Razibul Islam; Md Anisuzzaman; Khadijatul Kubra Riya; Takaomi Arai; Norhayati Ngah; M. Belal Hossain (Aquaculture International, 2026)

Retraction Note: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2026)

Xanthan gum-stabilized cocoa butter emulsion: characterization, molecular interactions, physicochemical stability, and bioaccessibility of α-mangostin - Naymul Karim; Ke Zhang; Mohammad Rezaul Islam Shishir; Mohammad Nasiruddin Rana; Gobinath Marappan; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Isam A. Mohamed Ahmed; Jitbanjong Tangpong; Xiaobo Zou (Food Chemistry, 2026)

Advances in green food processing technologies: Enhancing efficiency, safety, and sustainability - Asad Nawaz; Sana Irshad; Xiaofang Luo; Noman Walayat; Putri Widyanti Harlina; Zuodong Qin; Muhammad Afzaal; Fakhar Islam (Food Control, 2026)

Large-animal farmers’ knowledge, attitudes, and practices regarding antibiotic usage in dairy and beef fattening farms in Bangladesh’s milk pocket areas - Fardina Sultana Sumi; Kazi Rafiq; A. K. M. Anisur Rahman; Muhammad Tofazzal Hossain; Purba Islam; Md. Rakib Hasan; Shah Md. Iqbal; Anan Binte Zaman (Tropical Animal Health and Production, 2026)

Improving growth traits in rabbits: a comparative study of Gabali, New Zealand White, and their hybrids using 18S rDNA sequencing - Hairul Islam Mohamed Ibrahim; Abdullah Sheikh; Roshmon Thomas Mathew; Muhammad Munir; Gamal Bekhet; El-Sayed Hemdan Eissa; Sameh A. Abdelnour; Mohamed D. Mahran (Tropical Animal Health and Production, 2026)

Microencapsulation of Probiotics in Polymeric Microgels: Enhanced Viability and Stability through Inorganic Nanoparticle Doping - Muhammad Umar Farooq; Ashok Kumar Bishoyi; Nameer khairullah Mohammed; Suhas Ballal; Abhayveer Singh; Supriya S.; Faiyaz Ahmed; Laraib Shoukat; Noor Akram; Fakhar Islam (Probiotics and Antimicrobial Proteins, 2026)

Combining anxiolytic activity of thymol and trans-ferulic acid: a potential GABAergic intervention - Md. Hanif Munshi; Noshin Tasnim Yana; Imam Hossen Rakib; Emon Mia; Nusrat Jahan Tohfa; Md. Sakib Al Hasan; Md Abu Sayeed; Mst. Sumaia Akter; Md. Arif Hossain; Muhammad Torequl Islam; Md. Shimul Bhuia; Mushtaq Ahmad Ansari (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Ultra-trace Determination of Chromium (III) and Cobalt (II) Using Phosphonate Ester-Functionalized PAMAM Magnetite and DSPE-FAAS - Dilges Baskin; Ozge Yilmaz; Muhammad Nazrul Islam; Metin Tulu; Tarik Eren; İkbal Koyuncu (Bulletin of Environmental Contamination and Toxicology, 2026)

Impact of Drought on Agricultural Ecosystems, Biomass and Carbon Uptake in the Northern Part of Bangladesh Using Remote Sensing and Weather Station Data - Nur Hussain; Md Adnan Rahman; Muhammad Rezaul Rakib; Md. Nurul Islam; Md Kamruzzaman (Remote Sensing in Earth Systems Sciences, 2026)

Seaweed as a functional feed additive in aquaculture: Efficacy, safety, and fish species-specific optimization - Sahr Lamin Sumana; Gnoumasse Sidibe; Ahmed E. Elshafey; Damien Habinshuti; Agnes Mattia; Jusu Massaquoi; Sheku Tarawallie; Mukhtar Muhammad Abdullateef; Abubakar Shuaibu; Prince Tongor Mabey; Amidu Mansaray; Yang Xiaofei; et al. (Algal Research, 2026)

Piperine exerts anti-inflammatory effects and antagonises the properties of celecoxib and ketoprofen: in vivo and molecular docking studies - Rubel Hasan; Md. Shimul Bhuia; Raihan Chowdhury; Muhammad Ali Khan; Modhurima Mazumder; Noshin Tasnim Yana; Marcus Vinícius Oliveira Barros de Alencar; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (Natural Product Research, 2026)

Corrigendum to “Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar)” [Aquaculture Volume 612, Part 1, 15 January 2026, 743142]. - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

Influence of environmental and climatic factors on AOD concentration: A model-based analysis - Md. Tushar Ali; Ashiqur Rahman; Muhammad Harunur Rashid; Quazi Hamidul Bari; Abu Reza Md. Towfiqul Islam (Urban Climate, 2026)

Intelligent transformation of the tea industry: Artificial intelligence applications in management, harvesting, and processing - Xuechen Zhang; Sitan Ye; Yujie Wang; Mostafa Gouda; Yan Hu; Muhammad Adnan Islam; Yong He; Xiaoli Li (Trends in Food Science & Technology, 2026)

Comparative population parameters and stock assessment of three symmetric Scylla species in coastal waters of the Gulf of Thailand - Md. Rashedal Islam; Sukree Hajisamae; Siriporn Pradit; Muhammad Abdur Rouf; Sofiyudin Maae; Husneya Rensep (Regional Studies in Marine Science, 2026)

GeoFedNet: Federated learning for privacy-aware, robust, and generalizable seismic interpretation - Muhammad Saif ul Islam; Aamir Wali (Computers & Geosciences, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

Assessment of antiemetic potential of schaftoside through modulation of dopaminergic, serotonergic and muscarinic signaling pathways: in vivo and in silico investigations - Md. Shakil Ahmmed; Rakib Hossan; Tawfik Rakaiyat Ripu; Towfiqur Rahman; Mohammad Y. Alshahrani; Emon Mia; Proma Mandal; Md. Sakib Al Hasan; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Automatic weed detection in paddy field: a review - Md. Monirul Islam; Siti Khairunniza-Bejo; Muhammad Saiful Ahmad Hamdani; Nur Azuan Husin (Journal of Plant Diseases and Protection, 2026)

Gypsum-integrated, goethite-modified biochar enhances Cd and As immobilization in contaminated paddy soil under contrasting redox conditions - Iftikhar Ali Ahmad; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Geochemistry and Health, 2026)

Assessment of spatial and seasonal variation in soil heavy metal contamination adjacent to Chini Lake, Malaysia - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza (Environmental Geochemistry and Health, 2026)

Antihyperlipidemic activity of Kalanchoe blossfeldiana leaf extract: phytochemical, in vitro, in vivo, and in silico insights - Abdul Rehman Riaz; Muhammad Islam; Hamid Saeed (In Silico Pharmacology, 2026)

Health Risk Assessment of Women and Children Through Trace Elements from Biomass Cooking Fuels in Madhupur Tract Rural Community in Bangladesh - Muhammad Azizal Hoque; Niger Sultana; Sneha Gautam; Md. Al-Amin Khan; Md. Abdul Baten; M. Rafiqul Islam; Md. Badiuzzaman Khan (Aerosol Science and Engineering, 2026)

Mechanistic insights into the synergistic pharmacology of quercetin–kaempferol against SARS-CoV-2 infection - Farman Ali; Muhammad Zubair Saleem; Muhammad Mohsin; Saleem Ahmad; Waqar Islam; Wasim Qasim; Muhammad Tayyab (In Silico Pharmacology, 2026)

Investigation of the accumulation and sources of polycyclic aromatic hydrocarbons (PAHs) and mercury (Hg) in marine fish from the northern Bay of Bengal using a multi-tool approach - Md. Samrat Mohay Menul Islam; Afia Ibnat Saiba; Tashmem Al Faed; Lamyea Rahman; Muhammad Abu Bakar; Goutam Kumar Kundu (Marine Pollution Bulletin, 2026)

Effects of full-fat black soldier fly larvae and yellow mealworm meals on blood composition and liver health in Atlantic salmon (Salmo salar) - S.M. Majharul Islam; Mette Sørensen; Muhammad A.B. Siddik; Florence Perera Willora; Monica F. Brinchmann; Kirill Spiten; Kyla Zatti; Kim D. Thompson; Ioannis N. Vatsos (Aquaculture, 2026)

Deep organic amendments in vineyard subsoils reduce temperature sensitivity of respiration without increasing N2O or CH4 emissions - Muhammad ISLAM; Ralf WEHRLE; Stefan PÄTZOLD; Nele SCHNEIDER; Katja HERZOG; Nicolas BRÜGGEMANN (Pedosphere, 2026)

The role of personal, familial, and institutional factors on Gen Z's behavioral intentions toward food waste prevention - Muhammad Mehedi Masud; K. M. Anwarul Islam; Md. Fakhrudoza Bari; Abdul Alim Baser; Rulia Akhtar; Abdullah Al- Mamun (Environmental Development, 2026)

Harvesting lithium from brines via high-selectivity nanofiltration integrated with membrane distillation - Amir Aghaei; Muhammad Amirul Islam; Vahid Rad; Aria Khalili; Afrouz Yousefi; Ahamd Arabi Shamsabadi; Masoud Soroush; Jae-Young Cho; Young-Hye La; Mohtada Sadrzadeh (Chemical Engineering Journal, 2026)

Multifunctional Mg-MOF-74@Carvacrol/Chitin nanofiber-based nanocomposite film for enhanced food packaging - Muhammad Junaid Khan; Muhammad Rehan Islam; Farooq Hafeez; Chunyan He; Jun Zhang; Yunlei Xianyu (Chemical Engineering Journal, 2026)

A comprehensive insight on the bioactive phytochemicals and pharmacological propensities of Ficus benghalensis L.: a reservoir for modern drug discovery - Sulaman Yaqub; Muhammad Islam; Hamid Saeed; Abrar Ahmad; Khurram Aamir; Rida Naeem; Meerab Tanveer (Phytochemistry Reviews, 2026)

Succinic acid enhances sedative activity of diazepam through GABAergic receptor modulation: Evidence from behavioral approach and computational insights - Md. Sakib Al Hasan; Yasin Emon; Mohammad Y. Alshahrani; Imam Hossen Rakib; Emon Mia; Abida Sultana; Akayed Hasan; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Seed Priming with Osmolytes Ameliorates Salinity Tolerance in Maize (Zea mays L.) Through Embryonic Modifications - Paris Riaz; Ansa Asghar; Sana Fatima; Sana Basharat; Zahida Parveen; Mansoor Hameed; Farooq Ahmad; M. Sajid Aqeel Ahmad; Muhammad Ashraf; Faakeha Islam; Syed Mohsan Raza Shah; Qasim Ali (Journal of Plant Growth Regulation, 2026)

Enhancing generalization in seismic image segmentation through multi-dataset integration and transfer learning - Muhammad Saif ul Islam; Aamir Wali (Journal of Earth System Science, 2025)

Knowledge, attitude and practices of primary livestock raisers regarding anthrax and anthrax vaccination of livestock in outbreak and non-outbreak areas of Bangladesh - Ireen Sultana Shanta; Kamal Hossain; Syed Sayeem Uddin Ahmed; Melissa Kadzik; Antonio R. Vieira; Taifur Rahman; Rita M. Traxler; Md Saiful Islam; Farhana Haque; Muhammad Belal Hossain; Sk Shaheenur Islam; Nurnabi Ahmed; et al. (Preventive Veterinary Medicine, 2025)

Corrigendum to “Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression” [Fish Shellfish Immunol. 149 (2024) 109549] - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2025)

Polyamide thin film nanocomposite membranes modified with cationic nanogel for efficient Li+/Mg2+ separation - Elham Jashni; Amir Aghaei; Muhammad Amirul Islam; Amirhossein Taghipour; Forough Rezaie; Aria Khalili; Jae-Young Cho; Mohtada Sadrzadeh (Desalination, 2025)

Citric acid - crosslinked cellulose derivatives superabsorbent hydrogels (SAH) as sustainable alternatives for personal hygiene applications - Muhammad Shahidul Islam; Dylan Sproule; Jessica Yohans; Pansit Chenananporn; Evelyn Yim; Arvind Gupta; Tizazu H. Mekonnen (Chemical Engineering Journal, 2025)

Bacterial polysaccharides in the food industry: Synthesis-structure-properties relationships, AI-driven innovations, regulatory challenges, and bioeconomy prospects - Muhammad Wajid Ullah; Sehrish Manan; Khulood Fahad Alabbosh; Mazhar Ul-Islam; Omar Mohammad Atta; Asif Ali Khan; Yimin Fan; Khalid Ali Khan; Noureddine Elboughdiri; Zhiguo Wang (Carbohydrate Polymers, 2025)

Spatial assessment and ecological risk evaluation of soil heavy metal contamination using multivariate statistical techniques - Mir Sujaul Islam; Faiz Ul Hassan; Mohd Ekhwan Toriman; Raheel Ahmad; Muhammad Amjad Bashir; Abdur Rehim; Qurat-Ul-Ain Raza; Goh Choo Ta; Sharina Binti Abdul Halim (CATENA, 2025)

Nitrogen pollution and management in rice–wheat cropping system - Abdul Rehman; Ahmad Nawaz; Muhammad Islam; Fasih Ullah Haider; Muhammad Farooq (Plant and Soil, 2025)

Carbon Nanotubes Improve Quantitative and Qualitative Attributes of Potato (Solanum tuberosum L) Genotypes - Muhammad Ismail; Muhammad Imtiaz; Raham Sher Khan; Fazal Jalal; Fazal Said; Muhammad Ali Khan; Syed Hussain; Badshah Islam; Salman Khan; Sabir Khan; Atta Ullah; Maqsood Khan; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Molecular Epidemiology and Resistant Gene Mapping of Bacterial Isolates from Houbara bustards - Maham Fatima; Tasleem Kausar; Amjad Islam Aqib; Muhammad Shoaib; Farid S. Ataya; Mohamed Saad Daoud (Current Microbiology, 2025)

Weighted ensemble transfer learning with EfficientNet: Advancing salt body segmentation in seismic imaging - Muhammad Saif ul Islam; Aamir Wali (Computational Geosciences, 2025)

Biocontrol and beyond: the versatile roles of Streptomyces in agriculture - Tajrin Jahan; Muhammad Fazle Rabbee; Md. Mobinul Islam; Md. Ahsan Habib; Md. Sohel Rana; Avijicth Basak; Randa Mohammed Zaki; Md. Mohidul Hasan; Kwang-Hyun Baek (Reviews in Environmental Science and Bio/Technology, 2025)

Exploring asymmetric effects of blue economy sectors on economic growth: evidence from a non-linear ARDL analysis - Muhammad Mehedi Masud; K. M. Anwarul Islam; Rulia Akhtar; Abdullah Al-Mamun (Aquaculture International, 2025)

Ozone‐Tolerant Rice for Air‐Polluted Environments - Muhammad Shahedul Alam; Mirza Mofazzal Islam; Minh Khue Do; Blessing Omo Osimahon; Aishwarya Kushal Karki; Aleena Ittapad Baburajan; Marc Hartung; Sawitree Autarmat; Yanru Feng; Matthias Wissuwa; Michael Frei (Global Change Biology, 2025)
Recent decades have witnessed a surge in tropospheric ozone concentrations across many Asian countries, including Bangladesh, posing a significant threat to rice yields and regional food security. This study presents a comprehensive marker‐assisted breeding program designed to introgress two quantitative trait loci (QTL) conferring ozone tolerance into elite Bangladeshi rice varieties. We crossed the donor landrace Kasalath with high‐yielding varieties BRRI dhan28 and Binadhan‐11, generating BC 2 F 4 lines with an average of 87% recipient parent genome recovery. These lines harbored diverse combinations of positive alleles at the target QTLs while retaining the agronomic traits of modern rice varieties. In controlled open‐top‐chamber experiments, the presence of these QTLs in elite backgrounds mitigated ozone stress symptoms, reduced physiological damage such as lipid peroxidation or loss in photosynthetic CO 2 assimilation rates, and alleviated yield losses. Field trials conducted in a high ozone stress environment in Bangladesh, with and without the ozone protectant ethylenediurea (EDU), revealed that sensitive recipient parents suffered under ambient ozone concentrations. In contrast, the ozone‐tolerant lines exhibited significantly less yield loss and were less affected by pollution. Our findings demonstrate the efficacy of marker‐assisted breeding in adapting rice to changing atmospheric conditions, offering a robust strategy for safeguarding food security in the face of global change.

Trace Metal Contamination in Marine Fish Species: Implications for Food Safety and Human Health - Md. Samrat Mohay Menul Islam; Umme Hafsa Tuhin; Md. Ashraful Islam; Lutfunnesa Tamanna; Mahbub Alam; Muhammad Abu Bakar; Md. Manzoorul Kibria; Sreebash Chandra Battacherjee; Mohammad Shamsil Arafeen (Biological Trace Element Research, 2025)

FinTech, environmental innovation, and social capital drive environmental and economic development in Asia - Yun Li; Muhammad Naeem Shahid; Muhammad Umar Islam; Muhammad Ishtiaq; Falak Sher (Environment, Development and Sustainability, 2025)

A hybrid 3D CNN-LSTM model with soft spatial attention mechanism for accurate hyperspectral image classification - Mohamed Sultan Mohamed Ali; Md Sakib Bin Islam; Molla E. Majid; Saad Bin Abul Kashem; Amith Khandakar; Muhammad E.H. Chowdhury (Remote Sensing Applications: Society and Environment, 2025)

Mindsets matter: Reimagining the destination brand experience-environmental behaviour link through a cognitive lens - Muhammad I. Hossain; Arnold Japutra; Nurnobi Islam; Ammar Javed (Journal of Environmental Management, 2025)

Oleuropein modulates anti-inflammatory activity of celecoxib and ketoprofen through cyclooxygenase pathway: in vivo, in silico and pharmacokinetics approaches - Nishat Jahan; Manoj Mandal; Imam Hossen Rakib; Md. Sakib Al Hasan; Emon Mia; Noshin Tasnim Yana; Mohammed Alfaifi; Faisal H. Altemani; Rakib Hossan; Umme Habiba Sumaya; Ali Mohamod Wasaf Hasan; Md. Abu Sayeed; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Synergistic Sedative Activity of Indirubin on Diazepam in Thiopental Sodium-induced Sleeping Mice: A Potential GABAergic Transmission - Tamanna Khatun; Abdul Malik; Abdullah K. Alshememry; Rubel Hasan; Md.Shimul Bhuia; Raihan Chowdhury; Sabiha Fatima; Dipu Bishwas; Sonaly Akter Mukty; Ishrat Jahan Disha; Mehedi Hasan Bappi; Muhammad Torequl Islam (Molecular Neurobiology, 2025)

Arbuscular mycorrhizal fungi and soil microbial communities under nitrogen deposition in nutrient-limited grasslands: a systematic review - Muhammad Numan Ali; Md Akramul Islam; Saddam Saqib; Muhammad Sufhan Tahir; Tahir Saadu; Ans Saeed; Aqarab Husnain Gondal (Symbiosis, 2025)

Exploring nonstructural NS5B protein to design a multi-epitope-based vaccine against HCV: immuno-informatics approach - Nouman Ali; Adeeba Ali; Muhammad Sheraz Yousuf; Arsheen Rehman; Saad Muhammad Islam; Bilal Ilyas; Aamir Ali (In Silico Pharmacology, 2025)

Scenario analysis of Saudi Arabia's residential solar energy incentives - Sikandar Abdul Qadir; Amjad Ali; Md Tasbirul Islam; Muhammad Shahid (Utilities Policy, 2025)

Reducing greenhouse gas emissions and improving rice yield: The influence of cultivars, soil salinity, and nitrogen management - S.M. Mofijul Islam; Yam Kanta Gaihre; Mohammad Nazrul Islam; Tamal Patra Suvo; Bjoern Ole Sander; Muhammad Ashraful Habib; Aminul Islam; Swati Nayak; Upendra Singh; Toshihiro Hasegawa; Md. Rafiqul Islam (Science of The Total Environment, 2025)

Nano zero-valent iron engineered with microwave-prepared biochar for improved nickel immobilization in contaminated soil and growth of oil crop (Brassica napus) - Fakhir Hannan; Muhammad Ahsan Farooq; Ahsan Ayyaz; Muhammad Iqbal; Zaid Ulhassan; Kangni Zhang; Faisal Islam; Juanjuan Li; Iram Batool; Weijun Zhou (Journal of Environmental Chemical Engineering, 2025)

Impact of Untreated and Wetland Treated Sewage Water Irrigation on Microbiology of Vegetables Grown in Summer and Winter Season - Mahwish Ali; Sanam Islam Khan; Muhammad Imran; Abdul Haleem; Talmeez U. R. Rehman; Safia Ahmed (International Journal of Environmental Research, 2025)

Evaluating Tunnel Squeezing in the Lawi Hydropower Project, Chitral, Pakistan: Geological and Empirical Perspectives - Muhammad Tariq Niaz; Waqas Ahmed; Shah Faisal Khattak; Jehanzeb Khan; Luqman Ahmad; Ihtisham Islam; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Thermal Thresholds and Mechanical Behavior of Granitic Rocks from Northern Pakistan: Implications for Rock Engineering - Abdul Rahim Asif; Muhammad Sajid; Waqas Ahmed; Ihtisham Islam; Abid Nawaz; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Phenological and morphological adaptations of Japanese quince (Chaenomeles japonica—(Thunb.)Lindl. ex Spach.) [Rosaceae]: insights from palynology and leaf histology - Shoxista Samatova; Mirtemir Berdiyev; Babir Baysunov; Muhammad Zafar; Salman Majeed; Mohamed Fawzy Ramadan; Trobjon Makhkamov; Muhammad Rizwan Khan; Khawaja Shafique Ahmad; Qamar Abbas; Ankeela Pńisyer; Fakhr ul Islam (Genetic Resources and Crop Evolution, 2025)

Antiemetic Efficacy of Nodakenin Through Muscarinic, Dopaminergic, and Serotonergic Receptor Modulation: Combined Experimental and Computational Approach - Towfiqur Rahman; Feroz Khan Nun; Tawfik Rakaiyat Ripu; Md. Sakib Al Hasan; Md. Shakil Ahmmed; Mohammed Alfaifi; Faisal H. Altemani; Abdullah H. Altemani; Imam Hossen Rakib; Emon Mia; Md. Shimul Bhuia; Muhammad Torequl Islam (Cell Biochemistry and Biophysics, 2025)

Scalable antimicrobial air filters: polypropylene/rose bengal melt-blown nonwoven filters - Sahar Kalani; Muhammad Shahidul Islam; Jiaqing Li; John Rawlins; Valerie C.A. Ward; Tizazu H. Mekonnen (Chemosphere, 2025)

Assessing the Population Dynamics and Stock Status of the Orange Mud Crab Scylla olivacea (Herbst, 1796) in Two Oceanic Coasts of Thailand - Md. Rashedul Islam; Sukree Hajisamae; Siriporn Pradit; Muhammad Abdur Rouf; Sofiyudin Maae; Husneya Rensep (Thalassas: An International Journal of Marine Sciences, 2025)

Performance evaluation of mortar with high-volume cement replacement using locally sourced pumice and recycled glass waste - Muhammad Ali Wazir; Zia Ul islam; Hamzah Mohammed Ali; Osama Wali (Innovative Infrastructure Solutions, 2025)

Empowering Saudi Arabia's sustainable energy future: A LEAP-Based approach for balancing energy supply and demand - Muhammad Shahid; Amjad Ali; Sikandar Abdul Qadir; Md Tasbirul Islam (Utilities Policy, 2025)

Multi-strain Native Probiotics from the Asian Stinging Catfish (Heteropneustes fossilis) Enhance Growth, Blood Health, and Organ Morphology in the Host - Sadia Nusrat Sharna; Kaniz Fatema Nur; Atiqur Rahman; Nittyananda Chandra Das; Jesmin Akter; Mst. Halima Khatun; Sara Momtaj Chowdhury; S. M. Majharul Islam; Muhammad Tofazzal Hossain; Mahbubul Pratik Siddique; M Kabir Hossain; Mohd Golam Quader Khan; et al. (Probiotics and Antimicrobial Proteins, 2025)

Caffeine and sclareol take the edge off the sedative effects of linalool, possibly through the GABAA interaction pathway: molecular insights through in vivo and in silico studies - Muhammad Torequl Islam; Md. Sakib Al Hasan; Jannatul Ferdous; Noshin Tasnim Yana; Emon Mia; Imam Hossen Rakib; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Md. Shimul Bhuia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Anti-arthritic potential of linalool: in vitro, in vivo, and in silico mechanistic insights for safer therapeutic applications - Shoyaeb Ahammed; Raihan Chowdhury; Md. Sakib Al Hasan; Emon Mia; Md. Showkoth Akbor; Md. Tahajul Islam; Rokibul Islam Chowdhury; Md. Sabbir Hossain; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Amirul Islam; Zainab M. Almarhoon; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Acetylsalicylic acid and cancer: updates on the new potential of a nature-inspired drug - Abdur Rauf; Ahmed Olatunde; Md. Rezaul Islam; Zubair Ahmad; Nabia Hafeez; Hassan A. Hemeg; Muhammad Imran; Mohammad S. Mubarak; Giovanni Ribaudo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Daidzin Enhances the Anticonvulsion Effects of Carbamazepine and Diazepam, Possibly Through Voltage-Gated Sodium Channels and GABAA-Dependent Pathways - Muhammad Torequl Islam; Md. Sakib Al Hasan; Jannatul Ferdous; Shoyaeb Ahammed; Md. Shimul Bhuia; Salehin Sheikh; Noshin Tasnim Yana; Irfan Aamer Ansari; Siddique Akber Ansari; Md. Saifuzzaman (Molecular Neurobiology, 2025)

Evaluation of Aqueous Extracts of Some Medicinal Plants Against the Wild Radish—an Eco-Friendly Aproach to Control the Troublesome Weed - Muhammad Asaud Islam; Rizwan Maqbool; Abdul Khaliq; Muhammad Ather Nadeem; Muhammad Yaseen (Journal of Crop Health, 2025)

Enhancing Salt Tolerance in Tomato Crop Using Microbial Inoculants - Farheen Islam; Afshan Rahman; Hafiza Farhat; Urooj Muhammad Sharif; Nawal Gul; Areeba Aslam (Journal of Crop Health, 2025)

Long-term PM2.5 exposure in Bangladesh: identification of pollution hotspots, trends, sources and health risk assessment - Md. Arfan Ali; Mazen E. Assiri; Muhammad Bilal; Salman Tariq; Gerrit de Leeuw; M. Nazrul Islam; Yu Wang; Lama Alamri; Ayman S. Ghulam; Shamsuddin Shahid (Air Quality, Atmosphere & Health, 2025)

Petrography and geochemistry of the Dupi Tila formation: Implications for depositional environment and tectonics - Ummae Habiba Sultana; Md Shofiqul Islam; Yesmin Nahar Jolly; K. M. Mamun; Shirin Akter; Muhammad Omar Faruk; Maliha Anzuman; Md Masud Karim (Acta Geochimica, 2025)

Neuroprotective potential of the methanolic leaf extract of Cheilanthes tenuifolia in Swiss albino mice - Asraful Islam Rakib; Raihan Chowdhury; Md. Shimul Bhuia; Md. Sakib Al Hasan; Rubel Hasan; Siddique Akber Ansari; Irfan Aamer Ansari; Sarfaraz Ahmed; John Eversong Lucena de Vasconcelos; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (South African Journal of Botany, 2025)

Salvianolic acid A enhances sedative effect of diazepam through the GABAergic pathway: In vivo, molecular docking, and pharmacokinetics approaches - Imam Hossen Rakib; Mohd Shahnawaz Khan; Arusha Ayub; Md. Sakib Al Hasan; Mohammed Alfaifi; Md. Shimul Bhuia; Emon Mia; Noshin Tasnim Yana; Md. Nasimul Haque Shipon; Muhammad Torequl Islam (Neurotoxicology and Teratology, 2025)

Rice grain quality alteration through manipulation of parboiling procedures to affect the concentration of macro- and micro- nutrient elements, B-vitamins, inorganic toxicants, and bacterial contamination - Andrew Meharg; Mukhlesur Rahman; Manus Carey; Kathryn Ralphs; Jonathan McComb; Coalain McCreanor; Mahmud Sumon; Rafiqul Islam; Mohammed Uddin; Muhammad Siddique; Saiful Islam; Caroline Meharg (Food Chemistry, 2025)

Assessments of protodioscin’s antinociceptive and antidiarrheal properties: in vivo and in silico investigations on macromolecule binding affinity and modulatory effects - Pompa Rani Ghosh; Md. Sakib Al Hasan; Razina Rouf; Raihan Chowdhury; Balkrishnan Yadav; Emon Mia; Md. Tanvir Islam; Md. Rakibul Hasan; Siddique Akber Ansari; Irfan Aamer Ansari; Md. Shimul Bhuia; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cumulative effect of chronic thermal stress and glyphosate based herbicide exposure on blood parameters and cortisol levels of common carp (Cyprinus carpio) - Imran Khan; Fakhr Ul Islam; Naimat Ullah Khan; Hazrat Ali; Mohammad Attaullah; Muhammad Ikram Khan (Ecotoxicology, 2025)

Parity and breastfeeding are contributing factors for geographical differences in breast cancer risk - Boon Hong Ang; Shivaani Mariapun; Farahida Mohd Farid; Imelda Suhanti Ishak; Muhammad Faiz Md Taib; Asfarina Ab Rahim; Lenjai Anak Jembai; Tania Islam; Kartini Rahmat; Farhana Fadzli; Nur Aishah Mohd Taib; Cheng Har Yip; et al. (Cancer Causes & Control, 2025)

Spatiotemporal dynamics of water and sediment characteristics in Kaptai Lake: implications for sustainable management - Saifuddin Rana; Mohammad Shakil Khan; Farhan Azim; Muhammad Obaidullha; Ariful Islam Milon; Zobair Alam Sunny; Sk. Ahmad Al Nahid; Shahida Arfine Shimul (Environmental Monitoring and Assessment, 2025)

Memory-Enhancing Effects of Dauricine in Swiss Mice: Possible Molecular Interventions Through In Vivo and In Silico Studies - Md. Showkot Akbor; Md. Sakib Al Hasan; Mst. Farjanamul Haque; Zakir Husain; Md. Tahajul Islam; Md. Samim Hossen; Md. Shadin; Shoyaeb Ahammed; Noshin Tasnim Yana; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (NeuroMolecular Medicine, 2025)

Techno-economic analysis and life cycle assessment of green hydrogen production: A case study of Sur Industrial City in Oman - Noman Raza Sial; Malik Sajawal Akhtar; Muhammad Islam; Muhammad Abdul Qyyum; Rashid Al-Abri; Ahmed Al-Hatrooshi; Ala’a H. Al Muhtaseb (Sustainable Cities and Society, 2025)

Epigallocatechin 3-gallate-induced neuroprotection in neurodegenerative diseases: molecular mechanisms and clinical insights - Md. Rezaul Islam; Abdur Rauf; Sumiya Akter; Happy Akter; Md. Ibrahim Khalil Al-Imran; Samiul Islam; Meherun Nessa; Chaity Jahan Shompa; Md. Nabil Rihan Shuvo; Imtiaz Khan; Waleed Al Abdulmonem; Abdullah S. M. Aljohani; et al. (Molecular and Cellular Biochemistry, 2025)
Neurodegenerative diseases (NDs) are caused by progressive neuronal death and cognitive decline. Epigallocatechin 3-gallate (EGCG) is a polyphenolic molecule in green tea as a neuroprotective agent. This review evaluates the therapeutic effects of EGCG and explores the molecular mechanisms that show its neuroprotective properties. EGCG protects neurons in several ways, such as by lowering oxidative stress, stopping Aβ from aggregation together, changing cell signaling pathways, and decreasing inflammation. Furthermore, it promotes autophagy and improves mitochondrial activity, supporting neuronal survival. Clinical studies have demonstrated that EGCG supplementation can reduce neurodegenerative biomarkers and enhance cognitive function. This review provides insights into the molecular mechanisms and therapeutic potential of EGCG in treating various NDs. EGCG reduces oxidative stress by scavenging free radicals and enhancing antioxidant enzyme activity, aiding neuronal defense. It also protects neurons and improves cognitive abilities by inhibiting the toxicity and aggregation of Aβ peptides. It changes important cell signaling pathways like Nrf2, PI3K/Akt, and MAPK, which are necessary for cell survival, cell death, and inflammation. Additionally, it has strong anti-inflammatory properties because it inhibits microglial activation and downregulates pro-inflammatory cytokines. It improves mitochondrial function by reducing oxidative stress, increasing ATP synthesis, and promoting mitochondrial biogenesis, which promotes neurons’ survival and energy metabolism. In addition, it also triggers autophagy, a cellular process that breaks down and recycles damaged proteins and organelles, eliminating neurotoxic aggregates and maintaining cellular homeostasis. Moreover, it holds significant promise as an ND treatment, but future research should focus on increasing bioavailability and understanding its long-term clinical effects. Future studies should focus on improving EGCG delivery and understanding its long-term effects in therapeutic settings. It can potentially be a therapeutic agent for managing NDs, indicating a need for further research.

Integrated Application of Drought-Tolerant Phosphate Solubilizing Bacteria and Native P Source Improves P Availability with Sustainable Wheat Production - Hafiz Shahid Hussain; Saira Tabbasum; Naima Mahreen; Mahreen Yahya; Khansa Ejaz; Zoya Aslam; Muhammad Imtiaz; Ejaz ul Islam; Zahid Iqbal Sajid; Sumera Yasmin (Journal of Soil Science and Plant Nutrition, 2025)

Assessing the Role of Biostimulants in Affecting the Production of Radish and Eggplant - Muhammad Amjad Bashir; Qurat-Ul-Ain Raza; Abdur Rehim; Hafiz Muhammad Ali Raza; Asad Ismail Noor; Mir Sujaul Islam; Faiz-Ul-Hassan; Muhammad Zafar-Ul-Hye; Yucong Geng (Journal of Soil Science and Plant Nutrition, 2025)

Geochemical and mineralogical characterization of Carboniferous-Triassic shales in Peninsular Malaysia: implications for hydrocarbon potential and depositional model - Alidu Rashid; Numair Ahmed Siddiqui; Abdul Halim Abdul Latiff; Nisar Ahmed; Maqsood Ahmad; Muhammad Jamil; Sohag Ali; Md. Mahmodul Islam (Carbonates and Evaporites, 2025)

RETRACTED ARTICLE: Bond graph analysis of a three-link physiological motor control system: integrating simulation and muscle behavior - Armeen Saeed; Nadia Sultan; Najam-ul-Islam Muhammad; A. M. Mughal (Biological Cybernetics, 2025)

Simultaneous adsorption of cadmium and arsenic by goethite-modified rice straw-derived biochar in water and soil: interactive ion effects and co-adsorption mechanism - Iftikhar Ali Ahmad; Hongqing Hu; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Fei Miao; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Ayaz Ali (Environmental Monitoring and Assessment, 2025)

Anticancer activity of Jasminum sambac and its bioactive phytochemicals against the PI3K-AKT-mTOR pathway: A literature-based in silico study - Md. Sakib Al Hasan; Md. Shimul Bhuia; Raihan Chowdhury; Md. Shadin; Emon Mia; Noshin Tasnim Yana; Imam Hossen Rakib; Siddique Akber Ansari; Irfan Aamer Ansari; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (South African Journal of Botany, 2025)

Unpacking organizational capabilities and green Innovation for sustainable Performance: The role of environmental regulations in manufacturing industry - Hasnain Javed; Jianguo Du; Muhammad Farooq Islam (Journal of Cleaner Production, 2025)

A review on hydrogen production using decorated metal-organic frameworks by electrocatalytic and photocatalytic water splitting - Rana Adeel Mehmood; Awais Ali Aslam; Muhammad Javid Iqbal; Ali Hamza Sajid; Ameer Hamza; Hina Fatima Tahira; Izaz Ul Islam; Erdal Yabalak (Fuel, 2025)

Unveiling the anxiolytic and analgesic effects of citronellal in Swiss mice: in vivo and in silico insights into COX and GABAA receptor pathways - Muhammad Torequl Islam; Md. Sakib Al Hasan; Raihan Chowdhury; Emon Mia; Imam Hossen Rakib; Noshin Tasnim Yana; Heba A. S. El-Nashar; Siddique Akber Ansari; Irfan Aamer Ansari; Md. Amirul Islam; Zainab M. Almarhoon; William N. Setzer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

CaMKIIα-NpHR-Mediated Optogenetic Inhibition of DRG Glutamatergic Neurons by Flexible Optic Fiber Alleviates Chronic Neuropathic Pain - Jaisan Islam; Md Taufiqur Rahman; Muhammad Ali; Elina KC; Hyun Jik Lee; Sang Hwan Hyun; Young Seok Park (NeuroMolecular Medicine, 2025)

Learning-based estimation of cattle weight gain and its influencing factors - Muhammad Riaz Hasib Hossain; Rafiqul Islam; Shawn R. McGrath; Md Zahidul Islam; David Lamb (Computers and Electronics in Agriculture, 2025)

Boosted proton conduction in LAO electrolyte through Li segregation for High-Performance ceramic fuel cells - Nabeela Akbar; Muhammad Yousaf; M.A.K. Yousaf Shah; Jahangeer Ahmed; Asma Noor; Quazi Arif Islam; Yan Wu; Saad M. Alshehri; Naveed Mushtaq; Bin Zhu; Sara Paydar (Fuel, 2025)

Superhydrophilic wettability porous materials from construction tooil/water separation applications - Muhammad Naseem; Mansoor Sultan; Mazhar ul Islam; Abdul Kareem; Nisar Ali; Ibrahim Khan; Shakeel Ahmad; Farooq nawaz; Adnan Khan; Farman Ali; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; et al. (Fuel, 2025)

ENSO teleconnections and predictability of the boreal summer temperature over the Arabian Peninsula in C3S and Saudi-KAU seasonal forecast systems - Mansour Almazroui; M. Salman Khalid; Muhammad Adnan Abid; Irfan Ur Rashid; Shahzad Kamil; Haroon Siddiqui; M. Nazrul Islam; Muhammad Ismail; Muhammad Azhar Ehsan; Enda O'Brien; Mazen Asiri; Rayees Ahmed; et al. (Atmospheric Research, 2025)

Tissue-specific inhibition of brassinosteroids regulates panicle branching and grain yield in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Xiaoyu Guo; Daowen Wang; Guang Qi (Science China Life Sciences, 2025)

Functional characterization and structural prediction of hypothetical proteins in monkeypox virus and identification of potential inhibitors - Reana Raen; Muhammad Muinul Islam; Redwanul Islam; Md. Rabiul Islam; Tanima Jarin (Molecular Diversity, 2025)

Impact of ingested microplastics on phenotypic traits and biochemical parameters in Nile tilapia (Oreochromis niloticus) juvenile - Sheikh Mustafizur Rahman; Fatima Tuz Zohora; Tania Sultana Mohona; Momotaz Khanom; Md. Moshiur Rahman; Md. Golam Sarower; Muhammad Abdur Rouf; Md. Nazrul Islam; Roshmon Thomas Mathew; Yousef Ahmed Alkhamis; Yousof Naser Alrashada; Lamya Ahmed Alkeridis; et al. (Aquaculture International, 2025)

Bromelain as a natural anti-inflammatory drug: a systematic review - Taline Alves Nobre; Athanara Alves de Sousa; Irislene Costa Pereira; Álina Mara Carvalho Pedrosa-Santos; Luana de Oliveira Lopes; Nicole Debia; Heba A. S. El-Nashar; Mohamed El-Shazly; Muhammad Torequl Islam; João Marcelo de Castro e Sousa; Francisco Leonardo Torres-Leal (Natural Product Research, 2025)

Gigantol, a promising natural drug for inflammation: a literature review and computational based study - Raihan Chowdhury; Shimul Bhuia; Asraful Islam Rakib; Sakib Al Hasan; Manik Chandra Shill; Heba A. S. El-Nashar; Mohamed El-Shazly; Muhammad Torequl Islam (Natural Product Research, 2025)

Precision in Rice Variety Classification using Stacking-based Ensemble Learning - Md. Masudul Islam; Galib Muhammad Shahriar Himel; Golam Moazzam; Mohammad Shorif Uddin (Journal of Cereal Science, 2025)

Role of artificial intelligence in halal authentication and traceability: A concurrent review - Asad Nawaz; Atka Afzal; Ali Khatibi; Amar Shankar; Heena Madan; Hafiza Sana Faisal; Amna Shahbaz; Ifrah Usman; Nimra Zulfiqar; Farhan Saeed; Aftab Ahmed; Ali Imran; et al. (Food Control, 2025)

ECCDN-Net: A deep learning-based technique for efficient organic and recyclable waste classification - Md. Sakib Bin Islam; Md. Shaheenur Islam Sumon; Molla E. Majid; Saad Bin Abul Kashem; Mohammad Nashbat; Azad Ashraf; Amith Khandakar; Ali K. Ansaruddin Kunju; Mazhar Hasan-Zia; Muhammad E.H. Chowdhury (Waste Management, 2025)

Corrigendum to “Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies” [Trends in Food Science & Technology 153 (2024) 104695] - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2025)

Systematic review of the digestive fate of rice phenolic compounds: Insights into bioavailability, influencing factors, encapsulation strategies, and health implications - Halah Aalim; Mohammad Rezaul Islam Shishir; Nermeen Yosri; Muhammad Arslan; Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Naymul Karim; Xiaodong Zhai; Zhihua Li; Chenguang Zhou; Xiaobo Zou (Trends in Food Science & Technology, 2025)

A comprehensive overview on the occurrence and removal of per- and polyfluoroalkyl substances through adsorption and biodegradation - Muhammad Zeeshan; Shamas Tabraiz; Safeerul Islam Hashmi; Arfa Iqbal; Daniel Dittmann; Zohaib Abbas; Cecilia L. MacLeod; Aki Sebastian Ruhl (Bioresource Technology Reports, 2025)

Dust over Saudi Arabia from multisource data: case studies in winter and spring - Mazen E. Assiri; M. Nazrul Islam; Md Arfan Ali; Arjan O. Zamreeq; Ayman S. Ghulam; Muhammad Ismail (Air Quality, Atmosphere & Health, 2025)

Chemical characterization and biological activity investigation of Curculigo orchioides Gaertn. - Tuz Mia Nur Akhi; Irin Sultana; Abdullah Al Faroq; Md. Shimul Bhuia; M. Mohi Uddin Chowdhury; Rafiqul Haider; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Vegetos, 2025)

Fermentation and fortification of Sargassum linearifolium with multi-strain probiotics improves mucosal barrier status, inflammatory response and resistance to Vibrio harveyi infection in barramundi Lates calcarifer - Muhammad A.B. Siddik; David S. Francis; S.M. Majharul Islam; Michael J. Salini; Ravi Fotedar (Aquaculture, 2025)

Assessment of clot-lysing and membrane-stabilizing activity of gallic acid through cyclooxygenase-1 and plasminogen interaction pathways - Shriti Raj Kumari Sah; Md Sakib Al Hasan; Lalan Kumar Thakur; Md Shadin; Raihan Chowdhury; Shoyaeb Ahammed; Siddique Akber Ansari; Irfan Aamer Ansari; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Food Bioscience, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Impact of synbiotic on growth performance, histo-architectural modulation of lymphoid organ, hematology, blood biochemistry and humoral immune response in naked neck chicken - Hemayet Hossain; Harimurti Nuradji; Mohammad Yousuf Miah; Muhammad Nazrul Islam; Md. Saiful Islam Siddiqui (Tropical Animal Health and Production, 2025)

Impact of dairy wastewater on paddy rice cultivation, leachate microbes, and soil health under alternate wetting and drying irrigation - Juli Akter; Md. Touhidul Islam; Nusrat Jahan; Mohammed Mizanur Rahman; M. G. Mostofa Amin; Muhammad Tofazzal Hossain; A. K. M. Adham (Paddy and Water Environment, 2025)

Formation of particulate matter in the ambient air of Dhaka city, Bangladesh - Md. Yeasin Pabel; Md. Fakrul Islam; Muhammad Nurul Huda; Shahid Akhtar Hossain; M. Muhibur Rahman; Md. Mominul Islam (Air Quality, Atmosphere & Health, 2025)

A critical review of NO2 and AOD in major Asian cities: challenges, mitigation approaches and way forwards - Most Mastura Munia Farjana Jion; Abu Reza Md Towfiqul Islam; Mahir Shahrier; Md Yousuf Mia; Jannatun Nahar Jannat; Md Arfan Ali; Md Abdullah Al Masud; Md Firoz Khan; Muhammad Bilal; Abubakr M. Idris; Guilherme Malafaia (Air Quality, Atmosphere & Health, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

Changes monitoring in Hongjiannao Lake from 1987 to 2023 using Google Earth Engine and analysis of climatic and anthropogenic forces - Md. Enamul Huq; Xijun Wu; Akib Javed; Ying Dong; Bingbing Li; David Lopez-Carr; Jiang Wu; Jing Liu; Yaning Zhang; Fanping Zhang; Muhammad Riaz; Md. Nazirul Islam Sarker; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Characterization and identification of the key volatile and non-volatile substances of Vangueria madagascariensis J.F. Gmel fruits (Kirkir) and exploration of their binding interactions with olfactory and taste receptors using computational chemistry methodology - Haroon Elrasheid Tahir; Sulafa B.H. Hashim; Muhammad Arslan; Gustav Komla Mahunu; Mohammad Rezaul Islam Shishir; Li Zhihua; Suliman Khan; Abdalbasit Adam Mariod; Hamza A.M. Abaker; Howida Elkheir Ibrahim; Hesham R. El-Seedi; Zou Xiaobo (Food Chemistry, 2024)

Tangeretin exerts and modulates the anxiolytic effects of the GABAkine drugs diazepam and flumazenil in mice: Molecular interventions through animal behavior and molecular dynamic simulations - Zakir Husain; Md Saifiuzzaman; Md Shimul Bhuia; Jannatul Ferdous; Md Sakib Al Hasan; Mehedi Hasan Bappi; Md Showkot Akbor; Siddique Akber Ansari; Irfan Aamer Ansari; Md Amirul Islam; Muhammad Torequl Islam (Food Bioscience, 2024)

Food safety profile of university food handlers in Bangladesh: A multicenter cross-sectional study - Tahsin Ahmed Rupok; Shahnaz Parvin Sweety; Mst. Mahfuza Rahman; Most. Tasfia Rahman; Fahmida Zaman; Muhammad Radone Ahmed; Tanvirul Islam; Md. Nurnobi Islam; Md. Masud Rana; Abdur Rahman Riaz; Md. Golam Sadik (Food and Humanity, 2024)

Structure-property relationship of ultrasound-assisted nanoemulsion-impregnated bioactive polysaccharide films for enhanced shelf life of mushrooms - Asif Ali Khan; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Mazhar Ul-Islam; Syed Asim Shah Bacha; Umar Zeb; Fang-Jie Yao; Sulaiman Ali Alharbi; Mansour Shrahili; Yan Yang; Wei Jia; et al. (Food Packaging and Shelf Life, 2024)

Dairy farm waste: A potential reservoir of diverse antibiotic resistance and virulence genes in aminoglycoside- and beta-lactam-resistant Escherichia coli in Gansu Province, China - Muhammad Shoaib; Minjia Tang; Amjad Islam Aqib; Xuejing Zhang; Zhongyong Wu; Yang Wen; Xiao Hou; Jinpeng Xu; Ruochen Hao; Shengyi Wang; Wanxia Pu (Environmental Research, 2024)

Removal of airborne particulate matter by evergreen tree species in Dhaka, Bangladesh - Saif Shahrukh; Richard Baldauf; Robert Popek; Mohammad Moniruzzaman; Muhammad Nurul Huda; Md. Mominul Islam; Shahid Akhtar Hossain; Mohammad Enayet Hossain (Environmental Pollution, 2024)

Drought Priming Enhanced Grain Yield of Wheat Against Salinity Stress - Ashutus Singha; Jahidul Karim; Asif Adnan Prince; Nargis Akter; khalada Akter Runa; Muhammad Naqib; A. K. Mohibul Islam; Setu Roy; Jouadul Hasan (Water Conservation Science and Engineering, 2024)

PPG2RespNet: a deep learning model for respirational signal synthesis and monitoring from photoplethysmography (PPG) signal - Md Nazmul Islam Shuzan; Moajjem Hossain Chowdhury; Saadia Binte Alam; Mamun Bin Ibne Reaz; Muhammad Salman Khan; M. Murugappan; Muhammad E. H. Chowdhury (Physical and Engineering Sciences in Medicine, 2024)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Whole-exome sequencing identifies rare recessive variants in azoospermia patients from consanguineous Pakistani families - Islam Uddin; Iqra Zafar; Caoling Xu; Wenqing Li; Muhammad Imran Khan; Limin Wu; Jianqiang Bao (Molecular Genetics and Genomics, 2024)

Genetic variation, population structure, and cluster analysis of rice (Oryza sativa L.) genotypes using morphological characteristics and molecular markers - Mst Fatamatuzzohora; Md. Sayeedul Islam; Muhammad Fazle Rabbee; Md. Shahadat Hossain; Sang Gu Kang; Mohammad Nurul Matin (Cereal Research Communications, 2024)

Earthworm, Perionyx excavatus as an alternate protein source for Nile tilapia: Effects on growth performance, blood biochemistry, erythrocyte morphology and intestinal health - Bethi Das; S. M. Majharul Islam; Sudipta Kumar Nag; Al-Azim; Ioannis N. Vatsos; Muhammad A. B. Siddik (Aquaculture International, 2024)
Recently, an increasing disparity has emerged in the need for raw fish meal (FM) and its supply, along with the environmental and financial obstacles associated with its use. Therefore, increasing and elevating the diversity of alternative protein sources for aquaculture nutrition is imperative. The study investigated the impact of substituting FM protein with EW meal on the growth, haemato-biochemical response and intestinal histomorphology of Nile tilapia. Up to 20% fishmeal replacement with EW meal had no adverse effects on fish growth performance. A quadratic analysis of the final body weight and EW meal level indicated the best growth performance at 17.5% replacement. Fish fed the 40% replacement level had significantly decreased height and width of intestinal folds and number of mucosal goblet cells compared to the control. Although red and white blood cell counts were found unchanged between the control, the 10% and 20% replacement groups, a significantly higher number of white blood cells and a lower number of red blood cells were found in the 40% group compared to the control. Blood glucose level was the highest, while haemoglobin level was the lowest in the 40% group. In the same group, significantly higher frequencies of erythrocyte cellular and nuclear abnormalities were noted. Lipid droplet accumulation in the liver was significantly higher in the 40% group, whilst the 10% and 20% groups showed no significant difference compared to the control.

Occurrence, characteristics and distribution of microplastics in commercial marine fishes of the Bay of Bengal - Pronoy Mondal; Md. Sazedul Hoque; Md. Arifur Rahman; Md. Mahmudul Hasan; Suprakash Chakma; Muhammad Saiful Islam; Md. Shahjahan (Marine Pollution Bulletin, 2024)

Recent advances in delivering mangosteen-based phytochemicals using promising micro/nanocarriers: Formulation, outcomes, and perspectives - Naymul Karim; Mohammad Rezaul Islam Shishir; Gobinath Marappan; Suliman Khan; Sulafa B.H. Hashim; Halah Aalim; Muhammad Arslan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Md. Atiar Rahman; Jitbanjong Tangpong; et al. (Trends in Food Science & Technology, 2024)

Salt reduction in food products: A systematic review of clean-label ingredients and non-thermal technologies - Abdul Waheed Khan; Ume Roobab; Zhaomei Wang; Muhammad Mohsin Raza; Hira Nawazish; Fakhar Islam; Rana Muhammad Aadil (Trends in Food Science & Technology, 2024)

Trans-Ferulic acid reduces the sedative activity of diazepam in thiopental sodium-induced sleeping mice: A potential GABAergic transmission - Md. Shimul Bhuia; Md. Sakib Al Hasan; Raihan Chowdhury; Siddique Akber Ansari; Irfan Aamer Ansari; Muhammad Torequl Islam (Neurotoxicology and Teratology, 2024)

Copper stress in rice: Perception, signaling, bioremediation and future prospects - Md Mahfuzur Rob; Delara Akhter; Tariqul Islam; Debu Kumar Bhattacharjya; Muhammad Saad Shoaib Khan; Faisal Islam; Jian Chen (Journal of Plant Physiology, 2024)

A comprehensive review of deep learning techniques for salt dome segmentation in seismic images - Muhammad Saif Ul Islam; Aamir Wali (Journal of Applied Geophysics, 2024)

Maternal arsenic exposure modifies associations between arsenic, folate and arsenic metabolism gene variants, and spina bifida risk: A case‒control study in Bangladesh - Chih-Fu Wei; Gwen Tindula; Sudipta Kumer Mukherjee; Xingyan Wang; Sheikh Muhammad Ekramullah; D.M. Arman; Md Joynul Islam; Mubinul Azim; Asifur Rahman; Shamantha Afreen; Md Ziaddin; Benjamin C. Warf; et al. (Environmental Research, 2024)

Influence of probiotic strains on growth performance, carcass characteristics and seasonal changes of growing New Zealand white rabbits - Elwy A. Ashour; Islam M. Youssef; Ahmed I. Elsherbeni; Muhammad Arif; Guillermo Tellez-Isaias; Ahmed K. Aldhalmi; Ayman A. Swelum; Mohamed E. Abd El-Hack (Tropical Animal Health and Production, 2024)

Oleuropein: Chemistry, extraction techniques and nutraceutical perspectives-An update - Anees Ahmed Khalil; Md. Mominur Rahman; Abdur Rauf; Md. Rezaul Islam; Sultana Juhara Manna; Ammar Ahmed Khan; Samee Ullah; Muhammad Nadeem Akhtar; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Jesus Simal-Gandara (Critical Reviews in Food Science and Nutrition, 2024)

Chemical weed control in direct-seeded rice using drone and mist flow spray technology - Muhd Azlan Abd Ghani; Abdul Shukor Juraimi; Ahmad Suhaizi Mat Su; Muhammad Saiful Ahmad-Hamdani; A.K.M. Mominul Islam; Mst Motmainna (Crop Protection, 2024)

Mix and manage: Cultivar mixtures can maintain yield under high wheat blast disease pressure - Timothy J. Krupnik; Md. Harun-Or-Rashid; Dinabandhu Pandit; Rabiul Islam; Md. Khaled Hossain; José Mauricio Cunha Fernandes; Krishna Kanta Roy; Muhammad Rezaul Kabir; Sabine Stuerz; Pawan Kumar Singh; Golam Faruq (Crop Protection, 2024)

Investigating the role of geochemistry and geotechnical properties in landslide characterization and triggering mechanisms: A case study from Dir Upper, Khyber Pakhtunkhwa Pakistan - Ihtisham Islam; Waqas Ahmed; Muhammad Rizwan; Sami Ullah; Azmat Ullah Orakzai; Petros Petrounias (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

CO2 storage in natural gas hydrate reservoirs: A review on prospects and challenges ahead - Md Nahin Mahmood; Aurpita Sen Gupta; Muhammad Towhidul Islam (Next Research, 2024)

Agricultural productivity and rural poverty in China: The impact of land reforms - Irfan Ullah; Vishal Dagar; Tauhidul Islam Tanin; Alam Rehman; Muhammad Zeeshan (Journal of Cleaner Production, 2024)

From farm to function: Exploring new possibilities with jute nanocellulose applications - Amjad Farooq; Syed Rashedul Islam; Md. Al-Amin; Mohammed Kayes Patoary; Md Tanjim Hossain; Muhammad Tauseef Khawar; Zongqian Wang; Mingwei Tian (Carbohydrate Polymers, 2024)

Assessing Trace Metal-Based Human Health Risks for Commonly Used Body Soaps in Bangladesh - Ashraful Hoque; Taznova Anwar Tanbi; Nakshi Saha; Sabbir Howlader; Nobonita Sarker; Aminul Islam Chowdhury; Amitava Bandyopadhyay; Shahidul Islam; Muhammad Abu Bakar; Nur E. Alam; Ashok Kumar Chakraborty; Sumon Ganguli (Biological Trace Element Research, 2024)

Comparative toxicity of insecticides to the haemocytes of honeybee, Apis mellifera (Hymenoptera: Apidae) under laboratory conditions - Rehana Bibi; Munir Ahmad; Junaid Ali Siddiqui; Muhammad Tariq Raseed; Waqar Islam (International Journal of Tropical Insect Science, 2024)

Exploring Potential Human Health Risks Linked to Heavy Metal(Loid)s in Dietary Fishes: Utilizing Data-Driven and Computational Modelling Approaches - Pritom Bhowmik Akash; Sazal Kumar; Md. Saikoth Jahan; Muhammad Shafiqur Rahman; Md. Assraf Seddiky; Anti Sorker; Rafiquel Islam (Biological Trace Element Research, 2024)
There are significant concerns about the risks to human health posed by metal(loid) contamination in dietary fishes in Bangladesh. Therefore, this study aimed to evaluate heavy metal(loid) contamination in fish and their associated health risks using published data from 2000 to 2022. Additionally, the safe limit of fish consumption was estimated using the target hazard quotient (THQ) followed by computational modelling and artificial neural networks (ANN). Results showed that freshwater and herbivorous fishes pose the least non-cancer risks, whereas saltwater and carnivorous fishes pose the highest non-cancer risks to Bangladeshi consumers. However, freshwater and omnivorous fish consumption pose the highest cancer risks compared to all studied metal(loid)s. In particular, among the heavy metal(loid)s, As, Cr, Hg, and Ni pose significant cancer and non-cancer risks to Bangladeshi consumers. On the contrary, the ANN and Decision tree regression (DTR) characterized the dataset, simulation model, or data testing condition, reaching 94.7% accuracy and allowing us to measure the safest fish consumption limit. The herbivorous fishes are less contaminated and allow greater consumption (175.09 g day −1 ). Contrarily, the allowable intake rates of carnivorous and omnivorous fishes are 153.05 and 168.63 g day −1 , respectively. Besides, the safe consumption rate of saltwater fishes was 156.51 g day −1 , which was lower than freshwater (180.59 g day −1 ) and euryhaline fishes (182.17 g day −1 ). Therefore, this study will assist fish consumers in selecting less contaminated fish, ensuring safe consumption levels, and ultimately reducing health risks associated with metal(loid) contamination in fish.

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Micro and nano-encapsulated natural products in yogurt: An emerging trend to achieve multifunctional benefits in product quality and human health. - Mohammad Rezaul Islam Shishir; Md Saifullah; Sulafa B.H. Hashim; Halah Aalim; Muhammad Bilal; Suliman Khan; Gobinath Marappan; Haroon Elrasheid Tahir; Li Zhihua; Xiaodong Zhai; Muhammad Arslan; Farah Saleena Taip; et al. (Food Hydrocolloids, 2024)

Strengthening education and training programmes for medical physics in Asia and the Pacific: the IAEA non-agreement technical cooperation (TC) regional RAS6088 project - Noriah Jamal; Anchali Krisanachinda; Virginia Tsapaki; Md Rafiqul Islam; Supriyanto Pawiro; Muhammad Al Omari; Chai Hong Yeong; Thinn Thinn Myint; Muhammad Basim Kakakhel; Mohammad Hassan Kharita; Cheow Lei James Lee; Anas Ismail; et al. (Physical and Engineering Sciences in Medicine, 2024)

A potential toxicological risk assessment of heavy metals and pesticides in irrigated rice cultivars near industrial areas of Dhaka, Bangladesh - Muhammad Nurul Huda; Mohammad Harun-Ur-Rashid; Anowar Hosen; Mahafuga Akter; Md. Mominul Islam; Sharmin Zaman Emon; Asma Rahman; Zuairia Binte Jashim; Saif Shahrukh; Mohammad Ismail (Environmental Monitoring and Assessment, 2024)

Sedimentology and reservoir characterization of Upper Cretaceous Kawagarh Formation, Upper Indus Basin, Lesser Himalayas, Pakistan: inferences from petrography, SEM-EDS and petrophysics - Salman Ahmed Khattak; Muhammad Hanif; Sajjad Ahmad; Ihtisham Islam; George Kontakiotis; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Microplastics in agroecosystems: Soil-plant dynamics and effective remediation approaches - Muhammad Tayyab; Syed Shabi Ul Hassan Kazmi; Paolo Pastorino; Hafiz Sohaib Ahmed Saqib; Zaher Mundher Yaseen; Muhammad Sajid Hanif; Waqar Islam (Chemosphere, 2024)

Sediment management using bandal-like structures as nature-based solution - Md. Munsur Rahman; Shampa; Anisul Haque; Hajime Nakagawa; Hao Zhang; Ashiqur Rahman; Maruf Dustegir; Motaher Hossain; Muhammad Muktadir Hussain; Johurul Islam; Sudipta Kumar Hore (Environmental Fluid Mechanics, 2024)

Soil erosion susceptibility mapping of Hangu Region, Kohat Plateau of Pakistan using GIS and RS-based models - Fakhrul Islam; Liaqat Ali Waseem; Tehmina Bibi; Waqar Ahmad; Muhammad Sadiq; Matee Ullah; Walid Soufan; Aqil Tariq (Journal of Mountain Science, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Insect meal in aquafeeds: A sustainable path to enhanced mucosal immunity in fish - S.M. Majharul Islam; Muhammad A.B. Siddik; Mette Sørensen; Monica F. Brinchmann; Kim D. Thompson; David S. Francis; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Appraisal of metallic accumulation in the surface sediment of a fish breeding dam in Türkiye: A stochastical approach to ecotoxicological risk assessment - Bayram Yüksel; Fikret Ustaoğlu; Handan Aydın; Cem Tokatlı; Halim Topaldemir; Md Saiful Islam; Said Muhammad (Marine Pollution Bulletin, 2024)

Integrated study of GIS and Remote Sensing to identify potential sites for rainwater harvesting structures - Xingsheng Du; Aqil Tariq; Fakhrul Islam; Samman Aziz; Liaqat Ali Waseem; Muhammad Nasar Ahmad; Muhammad Amin; Naz Ul Amin; Shoaib Ali; Muhammad Aslam; Walid Soufan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Mucosal barrier status in Atlantic salmon fed rapeseed oil and Schizochytrium oil partly or fully replacing fish oil through winter depression - SM Majharul Islam; Florence Perera Willora; Mette Sørensen; Golam Rbbani; Muhammad A.B. Siddik; Kyla Zatti; Shruti Gupta; Ian Carr; Ester Santigosa; Monica F. Brinchmann; Kim D. Thompson; Ioannis N. Vatsos (Fish & Shellfish Immunology, 2024)

Spatial distribution of heavy metal abundance at distance gradients of roadside agricultural soil from the busiest highway in Bangladesh: A multi-index integration approach - Md. Saydul Islam; Md. Nur-E-Alam; Muhammad Anwar Iqbal; Md. Badiuzzaman Khan; Shamim Al Mamun; Md. Yunus Miah; Md. Rasheduzzaman; S. Appalasamy; Mohammed Abdus Salam (Environmental Research, 2024)

Impact of extreme weather events on mental health in South and Southeast Asia: A two decades of systematic review of observational studies - Muhammad Mainuddin Patwary; Mondira Bardhan; Md Atiqul Haque; Syed Moniruzzaman; Johanna Gustavsson; Md Maruf Haque Khan; Jenni Koivisto; Marium Salwa; Saidur Rahman Mashreky; A.K.M. Fazlur Rahman; Anika Tasnim; Md Redwanul Islam; et al. (Environmental Research, 2024)

Post-COVID-19 pandemic perspectives on the need for wastewater surveillance of pathogenic microorganisms, antibiotics, and antimicrobial resistance in South Asia - Paromita Chakraborty; Nihal Mohamed; Sancho Rajan; Magdalena Urbaniak; Anuppama Suresh; Soudip Saha; Mukesh Pasupuleti; Emadul Islam; P.G. Vinod; Muhammad Zaffar Hashmi (Current Opinion in Environmental Science & Health, 2024)

Microbiota and soil fauna mediate litter decomposition and associated carbon and nitrogen dynamics in mangrove blue carbon ecosystems: insights from a coastal lagoon in Malaysia - Mohammad Ahsanul Islam; Md Masum Billah; Mohd Hanafi Idris; Wan Mohd Rauhan Wan Hussin; Md Khurshid Alam Bhuiyan; Muhammad Shariefuddin Bin Mohd Sukeri; Abu Hena Mustafa Kamal (Hydrobiologia, 2024)

Examining drinking water quality: analysis of physico-chemical properties and bacterial contamination with health implications for Shangla district, Khyber Pakhtunkhwa, Pakistan - Muhammad Salam; Dong Bo; Fakhri Alam; Islam Uddin; Md. Nuralam Hossain; Faisal Hayat; Waheed Ullah (Environmental Geochemistry and Health, 2024)

Integrated sedimentary and diagenetic constraints for delineating the reservoir potential of Jurassic carbonate sequences in the autochthonous Samana Suk Formation, Attock-Cherat Nizampur Area, Pakistan - Muhammad Ibrar; Sajjad Khan; Mehboob Ur Rashid; George Kontakiotis; Ihtisham Islam; Hammad Tariq Janjuhah; Assimina Antonarakou (Carbonates and Evaporites, 2024)

Fermentation in aquafeed processing: Achieving sustainability in feeds for global aquaculture production - Muhammad A. B. Siddik; Billie B. Julien; S. M. Majharul Islam; David S. Francis (Reviews in Aquaculture, 2024)
Improving feed suitability and bolstering the global upsurge in fish production is a strategic challenge for aquaculture. The utilization of plant and animal derived ingredients in aquafeed for achieving sustainable in finfish aquaculture is affected by various factors, including the presence of antinutritional factors, lowered nutrient bioavailability, indigestible particles and microbial contaminants. Applying fermentation to overcome these problems in aquafeed ingredients has received considerable attention in recent years as fermentation provides health‐promoting probiotic benefits to host organisms. Fermentation has also been shown in many studies to improve nutrient availability and bioavailability of feed, increased palatability and digestibility and eliminate anti‐nutritional compounds in dietary feed ingredients, making them more easily digestible which eventually improve growth and health performance of fish. Therefore, it is imperative to accelerate the use of fermented feedstuffs as aquafeed if sustainable aquaculture is to be achieved. This review reported the various methods of fermentation, characteristics of fermented feed ingredients, factors that are considered during fermentation and overall nutritional quality of fermented feed ingredients for aquaculture production. The role of fermented feed ingredients for various farmed species in terms of growth, feed utilization, gut microbiota composition, immunity and disease resistance in fish is thoroughly discussed. The possible drawbacks associated with the fermentation process are also discussed in the article.

Evaluation of environmental impacts of cotton polo shirt production in Bangladesh using life cycle assessment - Shafiqul Islam; A.K.M. Mehedi Hasan; Muhammad Abdur Rahman Bhuiyan; Gajanan Bhat (Science of The Total Environment, 2024)

Evaluation of the potentials of rice varieties and water management practices for reducing human health risks associated with polluted river water irrigated rice in Bangladesh - Masahiro Tokumura; Jumpei Miyazaki; Mahmud Hossain; Anwar Hossain; Mohammad Raknuzzaman; Qi Wang; Yuichi Miyake; Takashi Amagai; Shigeki Masunaga; Shofiqul Islam; Muhammad Rafiqul Islam; Masakazu Makino (Science of The Total Environment, 2024)

Exploring how economic growth, renewable energy, internet usage, and mineral rents influence CO2 emissions: A panel quantile regression analysis for 27 OECD countries - Cem Işık; Umit Bulut; Serdar Ongan; Hasibul Islam; Muhammad Irfan (Resources Policy, 2024)

Financial regulations and sustainability: The role of energy price and climate policy uncertainty - Muhammad Shahbaz; Muhammad Saeed Meo; Hafiz Waqas Kamran; Muhammad Saif ul Islam (Journal of Environmental Management, 2024)

Evaluating the Effect of pH, Temperature and Concentration on Antioxidant and Antibacterial Potential of Spectroscopically, Spectrophotometrically and Microscopically Characterized Mentha Spicata Capped Silver Nanoparticles - Tahreem Tanveer; Shaukat Ali; Nazish Mazhar Ali; Muhammad Adeel Farooq; Muhammad Summer; Ali Hassan; Fareha Ali; Muhammad Irfan; Lubna Kanwal; Hafsa Shahzad; Rahila Islam (Journal of Fluorescence, 2024)

Biomonitoring potentially toxic elements in atmospheric particulate matter of greater Dhaka region using leaves of higher plants - Zuairia Binte Jashim; Saif Shahrukh; Shahid Akhtar Hossain; Jahan-E-Gulshan; Muhammad Nurul Huda; Md. Mominul Islam; Mohammad Enayet Hossain (Environmental Monitoring and Assessment, 2024)

Spatiotemporal variations, health risk assessment, and sources of potentially toxic elements in potamic water of the Anday Stream Basin (Türkiye), Black Sea Region - Cem Tokatli; Ekrem Mutlu; Fikret Ustaoğlu; Abu Reza Towfiqul Islam; Said Muhammad (Environmental Monitoring and Assessment, 2024)

Natural Isatin Derivatives Against Black Fungus: In Silico Studies - Md. Saddam Hossain; Md. Anisur Rahman; Prithbey Raj Dey; Md. Parvez Khandocar; Md. Yeakub Ali; Mahajabin Snigdha; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Current Microbiology, 2024)

Quantifying canopy nitrogen of Aman rice utilizing multi-temporal unmanned aerial systems - Maruf Hossain; Hasan Muhammad Abdullah; Tanvir Ahmmed; Md Giashuddin Miah; Moin Us Salam; Majharul Islam; Md Mizanur Rahman (Remote Sensing Applications: Society and Environment, 2024)

Integrated Continuous Process Design for Crystallisation, Spherical Agglomeration, and Filtration of Lovastatin - Cameron J. Brown; John McGinty; Muhammad T. Islam; Nazer Rajoub; Omid Arjmandi-Tash; Sara Ottoboni; Muhid Shahid; Stephanie J. Urwin; Ye Seol Lee; Magdalene W. S. Chong; Foteini Papathanasiou; Aruna S. Prakash; et al. (Journal of Pharmaceutical Innovation, 2024)
Purpose This work seeks to improve the particle processability of needle-like lovastatin crystals and develop a small-footprint continuous MicroFactory for its production. Methods General conditions for optimal spherical agglomeration of lovastatin crystals and subsequent product isolation are developed, first as batch processes, and then transferred to continuous MicroFactory operation. Results Methyl isobutyl ketone is a suitable bridging liquid for the spherical agglomeration of lovastatin. Practical challenges including coupling unit operations and solvent systems; mismatched flow rates and inconsistent suspension solid loading were resolved. The successful continuous production of lovastatin spherical agglomerates (D 50 = 336 µm) was achieved. Spherical agglomeration increased the density of the bulk lovastatin powder and improved product flowability from poor to good, whilst maintaining lovastatin tablet performance. Conclusion A continuous, integrated MicroFactory for the crystallisation, spherical agglomeration, and filtration of lovastatin is presented with improved product particle processability. Up to 16,800 doses of lovastatin (60 mg) can be produced per day using a footprint of 23 m 2 .

Health, environment, and sustainable development: evidence from panel data from ASEAN countries - Muhammad Azam; Faridul Islam; Salim Rashid (Air Quality, Atmosphere & Health, 2024)

Retraction Note: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md.Mominur Rahman; Md.Rezaul Islam; Sheikh Shohag; Md.Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md.Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md.Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2024)

Temperature, topography, woody vegetation cover and anthropogenic disturbance shape the orchids distribution in the western Himalaya - Karamit Hussain; Muhammad Ejaz-Ul-Islam Dar; Arshad Mahmood Khan; Taskeen Iqbal; Ansar Mehmood; Tariq Habib; Ihab Mohamed Moussa; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2024)

Dynamics of soil biota and nutrients at varied depths in a Tamarix ramosissima-dominated natural desert ecosystem: Implications for nutrient cycling and desertification management - Waqar Islam; Fanjiang Zeng; Afzal Ahmed Dar; Muhammad Sohail Yousaf (Journal of Environmental Management, 2024)

Abundance, Source Apportionment, and Surface Characteristics of Microplastics in Agricultural Soil in a Flood-Prone Area of Central Bangladesh - Muhammad Saiful Islam; Zahidul Islam; Dipa Islam (Water, Air, & Soil Pollution, 2024)

Rooftop rainwater harvesting potential for kitchen gardening in the Rawal watershed, Pakistan - Ghani Akbar; Shahid Hameed; Zafar Islam; Muhammad Asif; Arshad Ashraf (Arabian Journal of Geosciences, 2024)

Woody biomass derived nano lignin-enabled membrane with high structural stability for efficient wastewater treatment - Rabia Jalil Khan; Chun Yin Lau; Muhammad Usman Farid; Md Khairul Islam; Alicia Kyoungjin An; Jiang Yi; Shao-Yuan Leu (Process Safety and Environmental Protection, 2024)

Phytotoxicity Evaluation of Five Proton-Pump Inhibitors Through Plant-Based Eukaryotic Test Models - Muhammad Torequl Islam; Marcello Iriti; Miquel Martorell; Javad Sharifi-Rad (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Predicting long term regional drought pattern in Northeast India using advanced statistical technique and wavelet-machine learning approach - Shahfahad; Swapan Talukdar; Bonosri Ghose; Abu Reza Md. Towfiqul Islam; Md. Hasanuzzaman; Ishita Afreen Ahmed; Bushra Praveen; Asif; Aruna Paarcha; Atiqur Rahman; A. S. Gagnon; Muhammad Afzal (Modeling Earth Systems and Environment, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

2-Hydroxybenzohydrazide as a novel potential candidate against nociception, inflammation, and pyrexia: in vitro, in vivo, and computational approaches - Gowhar Ali; Nazar Ul Islam; Muhammad Qaim; Rahim Ullah; Muhammad Saeed Jan; Khadija Shabbiri; Muhammad Shafique; Muhammad Ayaz (Inflammopharmacology, 2024)

Using river restoration model to control riverbank erosion in the Old Brahmaputra river of Bengal Basin, Bangladesh - Muhammad Rezaul Rakib; Md Anarul Haque Mondol; Abu Reza Md. Towfiqul Islam; Md. Bazlar Rashid (Advances in Space Research, 2024)

Temporal variation of water quality parameters in the lacustrine of the Thrace Region, Northwest Türkiye - Cem Tokatlı; Abu Reza Md. Towfiqul Islam; Said Muhammad (Environmental Science and Pollution Research, 2024)

Engineering of metal organic framework (MOF) membrane for waste water treatment: Synthesis, applications and future challenges - Muhammad Umar Shahid; Tayyaba Najam; Mazharul Islam; Ahmed M. Hassan; Mohammed A. Assiri; Abdul Rauf; Aziz ur Rehman; Syed Shoaib Ahmad Shah; Muhammad Altaf Nazir (Journal of Water Process Engineering, 2024)

Remediation of Cd-polluted soil, improving Brassica napus L. growth and soil health with Hardystonite synthesized with zeolite, limestone, and green Zinc oxide nanoparticles - Fakhir Hannan; Muhamamd Iqbal; Faisal Islam; Muhammamd A. Farooq; Muhammad Bilal Shakoor; Ahsan Ayyaz; Muhammad Saad Shoaib Khan; Juanjuan Li; Qian Huang; Weijun Zhou (Journal of Cleaner Production, 2024)

The path of microplastics through the rare biodiversity estuary region of the northern Bay of Bengal - Al-Nure Mubin; Abu Reza Md. Towfiqul Islam; Mehedi Hasan; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Sha Alam; Md. Refat Jahan Rakib; Muhammad Saiful Islam; Nasima Momtaz; Venkatramanan Senapathi; Abubakr M. Idris; et al. (Journal of Contaminant Hydrology, 2024)

Systematic review and meta-analysis of the potential threats to respiratory health from microbial Bioaerosol exposures - Muhammad Anwar Iqbal; Sadia Afrin Siddiqua; Mohammad Omar Faruk; Abu Reza Md. Towfiqul Islam; Mohammed Abdus Salam (Environmental Pollution, 2024)

The application of multi-attribute decision making methods in integrated watershed management - Rana Muhammad Adnan Ikram; Sarita Gajbhiye Meshram; Mohd Abul Hasan; Xinyi Cao; Ehsan Alvandi; Chandrashekhar Meshram; Saiful Islam (Stochastic Environmental Research and Risk Assessment, 2024)

Expanded utilisation of microalgae in global aquafeeds - Muhammad A. B. Siddik; Mette Sørensen; S. M. Majharul Islam; Newton Saha; Md Arifur Rahman; David S. Francis (Reviews in Aquaculture, 2024)
Utilising novel ingredients in aquafeeds is necessary for the continued expansion and intensification of aquaculture production. Microalgae are utilised widely in aquaculture for a variety of purposes; as live feed for fish and shellfish larvae and juveniles, for the production of algae‐based meals and oils to replace marine derived raw materials in aquafeeds, and for the production of astaxanthin, the carotenoid that gives salmon flesh its characteristic reddish colour. Notably, long‐chain polyunsaturated fatty acids, amino acids, proteins, fibres, antioxidant pigments, vitamins and minerals are among the compounds in microalgae with great biological value. A growing collection of experimental data has demonstrated that these substances are crucial for increasing larval survival and enhancing the growth and well‐being of fish and shellfish. In this review, the processing of microalgae utilised as aquafeed ingredient, the health promoting compounds in microalgae and their role in growth, immunity and disease resistance of fish and shellfish are described and discussed. Simultaneously, major hurdles in the commercial use of microalgae in aquafeed, and future research and development perspectives are all critically discussed.

Can sustainable resource management overcome geopolitical risk? - Adnan Safi; Muhammad Haseeb; Madeeha Islam; Muhammad Umar (Resources Policy, 2023)

Assessment of heavy metal accumulation in dust and leaves of Conocarpus erectus in urban areas: Implications for phytoremediation - Atta ur rehman; Kousar Yasmeen; Fakhrul Islam; Shoaib Ahmad Anees; Aqil Tariq; Muhammad Zubair; Muhammad Bilal; Inayat Ur Rahman; Siddiq Ur Rahman; Wesam Atef Hatamleh (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Effect of heterogeneity on the diffusion of Pb in apatite for petrochronological applications: A multiscale approach to characterizing the influence of apatite chemistry and anisotropy on Pb diffusion - Matee Ullah; Urs Klötzli; Ce’cile Gautheron; Laurent Tassan-Got; Fakhrul Islam; Muhammad Younas; Kamran Shehzad; Muhammad Khubab; Muhammad Ibrar; Bilal Wadood (Lithos, 2023)

Formulation and characterization of choline oleate-based micelles for co-delivery of luteolin, naringenin, and quercetin - Islam Md Shimul; Rahman Md Moshikur; Fahmida Habib Nabila; Muhammad Moniruzzaman; Masahiro Goto (Food Chemistry, 2023)

Therapeutic potentials of ononin with mechanistic insights: A comprehensive review - Md. Shimul Bhuia; Mst Asma Aktar; Raihan Chowdhury; Jannatul Ferdous; Md Anisur Rahman; Md Sakib Al Hasan; Muhammad Torequl Islam (Food Bioscience, 2023)

Climate change reshaping plant-fungal interaction - Abdul Waheed; Yakoopjan Haxim; Waqar Islam; Mushtaq Ahmad; Murad Muhammad; Fatmah M. Alqahtani; Mohamed Hashem; Haron Salih; Daoyuan Zhang (Environmental Research, 2023)

Rainwater harvesting for agriculture development using multi-influence factor and fuzzy overlay techniques - Xiangtian Zheng; Abid Sarwar; Fakhrul Islam; Abdul Majid; Aqil Tariq; Muhammad Ali; Shazia Gulzar; Muhammad Ismail Khan; Muhammad Akmal Sardar Ali; Muhammad Israr; Ahsan Jamil; Muhammad Aslam; et al. (Environmental Research, 2023)

Assessing household fine particulate matter (PM2.5) through measurement and modeling in the Bangladesh cook stove pregnancy cohort study (CSPCS) - Md Mostafijur Rahman; Meredith Franklin; Nusrat Jabin; Tasnia Ishaque Sharna; Noshin Nower; Tanya L. Alderete; Alaa Mhawish; Anisuddin Ahmed; M.A. Quaiyum; Muhammad T. Salam; Talat Islam (Environmental Pollution, 2023)

Pb diffusion in perfect and defective zircon for thermo/petro-chronological investigations: An atomistic approach - Matee Ullah; Urs Klötzli; Bilal Wadood; Muhammad Khubab; Fakhrul Islam; Kamran Shehzad; Rafique Ahmad (Chemical Geology, 2023)

Hepatic β-arrestins: potential roles in liver health and disease - Alzahraa Muhammad Eissa; Mohamed H. Hassanin; Islam A. A. E. H. Ibrahim (Molecular Biology Reports, 2023)
Β-arrestins are intracellular scaffolding proteins that have multifaceted roles in different types of disorders. In this review article, we gave a summary about the discovery, characterization and classification of these proteins and their intracellular functions. Moreover, this review article focused on the hepatic expression of β-arrestins and their hepatocellular distribution and function in each liver cell type. Also, we showed that β-arrestins are key regulators of distinct types of hepatic disorders. On the other hand, we addressed some important points that have never been studied before regarding the role of β-arrestins in certain types of hepatic disorders which needs more research efforts to cover.

Influence of Phosphate Solubilizing Bacteria on the Growth of mustard Grown Under Drought Stress Conditions - Farhat Suhail; Aftab Afzal; Laraib Naseer; Aneela Pervaiz; Muhammad Ikram; Summaira Shaheen; Yasir Islam; Naeem Khan (Agricultural Research, 2023)

The nutraceutical properties and health benefits of pseudocereals: a comprehensive treatise - Muhammad Shahbaz; Nighat Raza; Mahad Islam; Muhammad Imran; Ishtiaque Ahmad; Arun Meyyazhagan; Karthika Pushparaj; Balamuralikrishnan Balasubramanian; Sungkwon Park; Kannan R. R. Rengasamy; Tanweer Aslam Gondal; Ahmed El-Ghorab; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Exploring the economic impact of institutional entrepreneurship, social Innovation, and poverty reduction on carbon footprint in BRICS countries: what is the role of social enterprise? - Fairtown Zhou Ayoungman; Abid Hossain Shawon; Rizwan Raheem Ahmed; Muhammad Kamran Khan; Md. Shoriful Islam (Environmental Science and Pollution Research, 2023)

RETRACTED ARTICLE: Demystifying the association between economic development, transportation, tourism, renewable energy, and ecological footprint in Bay of Bengal Initiative for Multi-Sectoral Technical and Economic Cooperation region during globalization mode - Muhammad Naveed; Minhazul Islam; Muhammad Usman; Mustafa Kamal; Mohammad Faisal Khan (Environmental Science and Pollution Research, 2023)

DNA base analysis: An effective tool to resolve taxonomic uncertainty and establish phylogenetic relationship in cryptic genotypes of Pyrus (pear), Rosaceae - Muhammad Saeed Akhtar; Shahid Ullah Khan; Ebraheem Abdu Musad Saleh; Said Muhammad; Mohammad Islam; Umber Zaman; Khalil ur Rehman; Gul Nawab; Muhammad Naveed Akhtar; Nabil A. Alhakamy; M.K. Rasha Ibrahim; Ehab A. Abdelrahman (South African Journal of Botany, 2023)

Towards achieving university sustainability! Linking social responsibility with knowledge sharing in Saudi universities - Afroze Nazneen; Islam Elgammal; Zubair Rashid Khan; Muhammad Haroon Shoukat; Ali Elsayed Shehata; Kareem M. Selem (Journal of Cleaner Production, 2023)

Coal mine wastes: Effective mitigation of coal waste slurry and acid mine drainage through bioflocculation using mixotrophic bacteria as bioflocculants - Siti Khodijah Chaerun; Erian Jeremy; Raudhatul Islam Chaerun; Riri Lidya Fathira; Muhammad Iqbal Toynbee; Supandi Supandi; Tsutomu Sato (International Journal of Coal Geology, 2023)

Corrigendum to “Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data” - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh; et al. (Groundwater for Sustainable Development, 2023)

Terrestrial and groundwater storage characteristics and their quantification in the Chitral (Pakistan) and Kabul (Afghanistan) river basins using GRACE/GRACE-FO satellite data - Aqil Tariq; Shoaib Ali; Iqra Basit; Ahsan Jamil; Nizom Farmonov; Behnam Khorrami; Muhammad Mohsin Khan; Samira Sadri; Muhammad Yousuf Jat Baloch; Fakhrul Islam; Muhammad Bilawal Junaid; Wesam Atef Hatamleh (Groundwater for Sustainable Development, 2023)

Antiemetic effects of sclareol, possibly through 5-HT3 and D2 receptor interaction pathways: In-vivo and in-silico studies - Mehedi Hasan Bappi; Abdullah Al Shamsh Prottay; Khattab Al-Khafaji; Md Showkoth Akbor; Muhammad Kamal Hossain; Md Shahazul Islam; Afia Ibnath Asha; Cassio Rocha Medeiros; Catarina Martins Tahim; Elaine Cristina Pereira Lucetti; Henrique Douglas Melo Coutinho; Hossam Kamli; et al. (Food and Chemical Toxicology, 2023)

CIMCA: Infusing computational intelligence in multi-criteria analysis to assess groundwater potential for recharge - Rashed Uz Zzaman; Muhammad Ali Nayeem; Sara Nowreen; Imran Hossain Newton; AKM Saiful Islam; Anwar Zahid; M. Sohel Rahman (Environmental Modelling & Software, 2023)

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Analyzing asymmetric ecological performance under structural change, technological innovation, and trade diversification: fresh insights from the USA - Md Minhazul Islam; Paiman Ahmad; Maria Shabir; Muhammad Usman; Mustafa Kamal (Environmental Science and Pollution Research, 2023)

Ranking Ship Detection Methods Using SAR Images Based on Machine Learning and Artificial Intelligence - Muhammad Yasir; Abdoul Jelil Niang; Md Sakaouth Hossain; Qamar Ul Islam; Qian Yang; Yuhang Yin (Journal of Marine Science and Engineering, 2023)
We aimed to improve the performance of ship detection methods in synthetic aperture radar (SAR) images by utilizing machine learning (ML) and artificial intelligence (AI) techniques. The maritime industry faces challenges in collecting precise data due to constantly changing sea conditions and weather, which can affect various maritime operations, such as maritime security, rescue missions, and real-time monitoring of water boundaries. To overcome these challenges, we present a survey of AI- and ML-based techniques for ship detection in SAR images that provide a more effective and reliable way to detect and classify ships in a variety of weather conditions, both onshore and offshore. We identified key features frequently used in the existing literature and applied the graph theory matrix approach (GTMA) to rank the available methods. This study’s findings can help users select a quick and efficient ship detection and classification method, improving the accuracy and efficiency of maritime operations. Moreover, the results of this study will contribute to advancing AI- and ML-based techniques for ship detection in SAR images, providing a valuable resource for the maritime industry.

Nanoparticle-laden contact lens for controlled release of vancomycin with enhanced antibiotic efficacy - Woei Yenn Tong; Wen-Nee Tan; Muhammad Afif Kamarul Azizi; Chean Ring Leong; Islam H. El Azab; Jun Wei Lim; M.H.H. Mahmoud; Daniel Joe Dailin; Mohamed M. Ibrahim; Lai Fatt Chuah (Chemosphere, 2023)

Removal efficiencies of microplastics of the three largest drinking water treatment plants in Bangladesh - Muhammad Saiful Islam; Zahidul Islam; A.H.M. Shofiul Islam Molla Jamal; Nasima Momtaz; Sadia Afrin Beauty (Science of The Total Environment, 2023)

Could climate change exacerbate droughts in Bangladesh in the future? - Mahfuzur Rahman; Md Sakib Hasan Tumon; Md Monirul Islam; Ningsheng Chen; Quoc Bao Pham; Kashif Ullah; Sumaiya Jarin Ahammed; Sharmina Naznin Liza; Md Abdul Aziz; Salit Chakma; Muhammad Esmat Enan; Md. Alomgir Hossain; et al. (Journal of Hydrology, 2023)

Changes in environmental degradation parameters in Bangladesh: The role of net savings, natural resource depletion, technological innovation, and democracy - Md. Monirul Islam; Muhammad Shahbaz; Tanzila Sultana; Zhaohua Wang; Kazi Sohag; Shujaat Abbas (Journal of Environmental Management, 2023)

Fabrication of a novel nanocomposite (TiO2/WO3/V2O5) by hydrothermal method as catalyst for hazardous waste treatment - Umer Younas; Awais Ahmad; Aftab Islam; Faisal Ali; Muhammad Pervaiz; Aimon Saleem; Muhammad Waseem; Ahmed Muteb Aljuwayid; Mohamed A. Habila; Salman Raza Naqvi (Fuel, 2023)

Anxiolytic-like effect of succinic acid: A possible GABAergic intervention - Md. Nayem Mia; Shanita Zaman Smrity; Mehedi Hasan Bappi; Hossam Kamli; Tawhida Islam; Abdullah Al Shamsh Prottay; Md. Showkoth Akbor; Md. Abdul Latif; Shoriful Islam; Kushal Bhakta; Manik Chandra Shill; Francisco Claudeni Pereira de Sousa; et al. (Food Bioscience, 2023)

Recent insights into pesticide resistance mechanisms in Plutella xylostella and possible management strategies - Muhammad Shehzad; Imran Bodlah; Junaid Ali Siddiqui; Muhammad Adnan Bodlah; Ammara Gull E Fareen; Waqar Islam (Environmental Science and Pollution Research, 2023)

The pervasiveness of microplastic contamination in the gastrointestinal tract of fish from the western coast of Bangladesh - Marhaba Matluba; Md. Kawser Ahmed; K.M. Azam Chowdhury; Nasim Khan; Md. Asrafur Rahman Ashiq; Muhammad Saiful Islam (Marine Pollution Bulletin, 2023)

Phytochemical screening and evaluation of antioxidant, anti-inflammatory, antimicrobial, and membrane-stabilizing activities of different fractional extracts of Grewia nervosa (Lour.) Panigrahi - Mehanaz Islam; Abdullah Al Shamsh Prottay; Irin Sultana; Abdullah Al Faruq; Mehedi Hasan Bappi; Md. Showkoth Akbor; Afia Ibnath Asha; Md. Munnaf Hossen; Pedro Esau Macedo Machado; Inacio Jose Secundo Junior; Henrique Douglas Melo Coutinho; Muhammad Torequl Islam (Food Bioscience, 2023)

Citrinin as a potential anti-cancer therapy: A comprehensive review - Ag-Anne P.M. de Menezes; Raí P.S. Aguiar; José V.O. Santos; Chandan Sarkar; Muhammad T. Islam; Antonio L. Braga; Mohammad M. Hasan; Felipe C.C. da Silva; Javad Sharifi-Rad; Abhijit Dey; Daniela Calina; Ana A.C. Melo-Cavalcante; et al. (Chemico-Biological Interactions, 2023)

Isolation of two new triterpene glycoside from the fruits of Terminalia arjuna and their in vitro and in silico studies - Rashadul Hossain; Rajia Sultana; Md. Din Islam; Shahed Zaman; Muhammad Iqbal Choudhary (Natural Product Research, 2023)

Brazilin: An updated literature-based review on its promising therapeutic approaches and toxicological studies - Sarmin Jamaddar; Chandan Sarkar; Shamima Akter; Mohammad S. Mubarak; Heba A.S. El-Nashar; Mohamed El-Shazly; Muhammad Torequl Islam (South African Journal of Botany, 2023)

A changing coastal ecosystem: Cox’s Bazar in southeastern coastal region of Bangladesh - Md. Giashuddin Miah; Md. Rafiqul Islam; Joyashree Roy; Md. Mezanur Rahman; Hasan Muhammad Abdullah (Environment, Development and Sustainability, 2023)

Biometric indices, growth pattern, and physiological status of captive-reared indigenous Yellowtail brood catfish, Pangasius pangasius (Hamilton, 1822) - Md. Arifur Rahman; Md. Rased Khan Manon; Md. Rahamat Ullah; Asraful Alam; Md. Jakiul Islam; Muhammad A. B. Siddik; Mohammed Mahbub Iqbal (Environmental Science and Pollution Research, 2023)

Anticancer effects of phytol against Sarcoma (S-180) and Human Leukemic (HL-60) cancer cells - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Ana Maria Oliveira Ferreira da Mata; Antonielly Campinho dos Reis; Rosália Maria Torres de Lima; José Roberto de Oliveira Ferreira; João Marcelo de Castro e Sousa; Paulo Michel Pinheiro Ferreira; Ana Amélia de Carvalho Melo-Cavalcante; Abdur Rauf; Hassan A. Hemeg; Khalaf F. Alsharif; et al. (Environmental Science and Pollution Research, 2023)

A critical review and prospect of NO2 and SO2 pollution over Asia: Hotspots, trends, and sources - Most. Mastura Munia Farjana Jion; Jannatun Nahar Jannat; Md. Yousuf Mia; Md. Arfan Ali; Md. Saiful Islam; Sobhy M. Ibrahim; Subodh Chandra Pal; Aznarul Islam; Aniruddha Sarker; Guilherme Malafaia; Muhammad Bilal; Abu Reza Md Towfiqul Islam (Science of The Total Environment, 2023)

Subsample stability, change detection and dynamics of oil and metal markets: A recursive approach - Asad Ul Islam Khan; Muhammad Shahbaz; Ayuba Napari (Resources Policy, 2023)

Mapping environmental sustainability of knitted textile production facilities - Md. Shamsuzzaman; Md Mazedul Islam; H M Rakib Ul Hasan; Adnan Maroof Khan; Abu Sadat Muhammad Sayem (Journal of Cleaner Production, 2023)

Targeting SARS-CoV-2 non-structural protein 13 via helicase-inhibitor-repurposing and non-structural protein 16 through pharmacophore-based screening - Md. Nazmus Samdani; Niaz Morshed; Rumman Reza; Muhammad Asaduzzaman; Abul Bashar Mir Md. Khademul Islam (Molecular Diversity, 2023)

Indoor thermal management of a public transport with phase change material (PCM) - Hasibuzzaman Mahmud; Mufrad Islam; Muhammad Ershad Jaman Khan; Dewan Hasan Ahmed (Energy, Ecology and Environment, 2023)

Estimating ground-level PM2.5 using subset regression model and machine learning algorithms in Asian megacity, Dhaka, Bangladesh - Abu Reza Md. Towfiqul Islam; Mohammed Al Awadh; Javed Mallick; Subodh Chandra Pal; Rabin Chakraborty; Md. Abdul Fattah; Bonosri Ghose; Most. Kulsuma Akther Kakoli; Md. Aminul Islam; Hasan Raja Naqvi; Muhammad Bilal; Ahmed Elbeltagi (Air Quality, Atmosphere & Health, 2023)

Instance segmentation ship detection based on improved Yolov7 using complex background SAR images - Muhammad Yasir; Lili Zhan; Shanwei Liu; Jianhua Wan; Md Sakaouth Hossain; Arife Tugsan Isiacik Colak; Mengge Liu; Qamar Ul Islam; Syed Raza Mehdi; Qian Yang (Frontiers in Marine Science, 2023)
It is significant for port ship scheduling and traffic management to be able to obtain more precise location and shape information from ship instance segmentation in SAR pictures. Instance segmentation is more challenging than object identification and semantic segmentation in high-resolution RS images. Predicting class labels and pixel-wise instance masks is the goal of this technique, which is used to locate instances in images. Despite this, there are now just a few methods available for instance segmentation in high-resolution RS data, where a remote-sensing image’s complex background makes the task more difficult. This research proposes a unique method for YOLOv7 to improve HR-RS image segmentation one-stage detection. First, we redesigned the structure of the one-stage fast detection network to adapt to the task of ship target segmentation and effectively improve the efficiency of instance segmentation. Secondly, we improve the backbone network structure by adding two feature optimization modules, so that the network can learn more features and have stronger robustness. In addition, we further modify the network feature fusion structure, improve the module acceptance domain to increase the prediction ability of multi-scale targets, and effectively reduce the amount of model calculation. Finally, we carried out extensive validation experiments on the sample segmentation datasets HRSID and SSDD. The experimental comparisons and analyses on the HRSID and SSDD datasets show that our model enhances the predicted instance mask accuracy, enhancing the instance segmentation efficiency of HR-RS images, and encouraging further enhancements in the projected instance mask accuracy. The suggested model is a more precise and efficient segmentation in HR-RS imaging as compared to existing approaches.

3D porous superoleophilic/hydrophobic grapefruit peel aerogel for efficient removal of emulsified-oil from water - Muhammad Imran; Ashraful Islam; Fatima Ismail; Panyue Zhang; Majid Basharat; Muhammad Ikram; Ahmed Uddin; Shah Zeb; Qadeer-Ul Hassan; Yongxiang Gao (Journal of Environmental Chemical Engineering, 2023)

Amentoflavone derivatives significantly act towards the main protease (3CLPRO/MPRO) of SARS-CoV-2: in silico admet profiling, molecular docking, molecular dynamics simulation, network pharmacology - Dipta Dey; Rajib Hossain; Partha Biswas; Priyanka Paul; Md. Aminul Islam; Tanzila Ismail Ema; Bibhuti Kumar Gain; Mohammad Mehedi Hasan; Shabana Bibi; Muhammad Torequl Islam; Md. Ataur Rahman; Bonglee Kim (Molecular Diversity, 2023)

Microplastics in freshwater wild and farmed fish species of Bangladesh - Nahid Sultana; Rafsana Rahman Tista; Muhammad Saiful Islam; Mahmuda Begum; Shanzida Islam; M. Niamul Naser (Environmental Science and Pollution Research, 2023)

Effects of straw incorporation and straw-burning on aggregate stability and soil organic carbon in a clay soil of Bangladesh - Milton Halder; Shahnewaz Jim Ahmad; Tanvir Rahman; Jagadish Chandra Joardar; Md. Abu Bakar Siddique; Muhammad Saiful Islam; Mahbub Ul Islam; Shuai Liu; Sheikh Rabbi; Xinhua Peng (Geoderma Regional, 2023)

Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Md. Huzzatul Islam; Sangee Sarkar Shanta; Muhammad Iqbal Hossain; Muhammed Ali Hossain; Md. Monower Hossain; Ebna Habib Md. Shofiur Rahaman; Abdullah Al Mahmud; Md. Abdullah Yousuf Akhond; Louise Sullivan; David E. L. Cooke; Geert J. T. Kessel; Louise R. Cooke; et al. (Potato Research, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans , is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl . A subset of 24 isolates all had mitochondrial DNA haplotype Ia. Samples of P. infestans DNA (124) from infected potato foliage obtained from Bangladesh (2014–2019) were genotyped by 12-plex SSR. The vast majority (95%) were assigned to EU_13_A2, which was present in every year in which samples were collected. Numerous EU_13_A2 variants were identified, many specific to Bangladesh. Six samples (from 2017 to 2019) had genotypes distinct from EU_13_A2 and with no close match to known European lineages. It is concluded that the current P. infestans population of Bangladesh is dominated by the aggressive lineage EU_13_A2, also dominant in India and Pakistan. The implications of this for control of late blight are discussed.

Oxidative stress mediated cytogenotoxicological effects of phytol in wistar albino rats - Marcus Vinícius Oliveira Barros de Alencar; Muhammad Torequl Islam; Antonielly Campinho dos Reis; José Victor de Oliveira Santos; Adriana Maria Viana Nunes; Felipe Cavalcante Carneiro da Silva; Keylla da Conceição Machado; João Marcelo de Castro e Sousa; Željko Reiner; Miquel Martorell; Sharmila Fagoonee; Javad Sharifi-Rad; et al. (Advances in Traditional Medicine, 2023)

Multipurpose plants utilization and resource management in Musk Deer National Park, Western Himalayas of Kashmir - Farooq Ahmed; Muhammad Ejaz Ul Islam Dar; Muhammad Jamil Ahmed; Tariq Habib; Liaquat Ali Khan (Environment, Development and Sustainability, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Comparative genomics with evolutionary lineage in Streptomyces bacteria reveals high biosynthetic potentials - Khorshed Alam; Md. Mahmudul Islam; Saiful Islam; Jinfang Hao; Muhammad Nazeer Abbasi; Muhammad Hayat; Muhammad Shoaib; Youming Zhang; Aiying Li (World Journal of Microbiology and Biotechnology, 2023)

Sarcococca saligna ameliorated D-galactose induced neurodegeneration through repression of neurodegenerative and oxidative stress biomarkers - Uzma Saleem; Zunera Chauhdary; Sumera Islam; Aimen Zafar; Rana O. Khayat; Norah A. Althobaiti; Ghulam Mujtaba Shah; Mohammed Alqarni; Muhammad Ajmal Shah (Metabolic Brain Disease, 2023)

Influence of rangeland protection and seasonal grazing on aboveground vegetation, forage quality and weight gain of small ruminants — a study in Thar Desert, Pakistan - Muhammad Islam; Abdul Razzaq; Sawsan Hassan; Muhammad Zubair; Muhammad Waseem Kalroo; Attaullah Khan; Shamim Gul; Sarfraz Ahmad; Barbara Ann Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2023)

Evaluating the safety and efficacy of daprodustat for anemia of chronic kidney disease: a meta-analysis of randomized clinical trials - Kaneez Fatima; Warda Ahmed; Asad Saulat Fatimi; Omar Mahmud; Muhammad Umar Mahar; Ayesha Ali; Syed Roohan Aamir; Muhammad Taha Nasim; Muhammad Bilal Islam; Muhammad Talha Maniya; Dua Azim; Shayan Marsia; et al. (European Journal of Clinical Pharmacology, 2022)

Modeling the fecal contamination (fecal coliform bacteria) in transboundary waters using the scenario matrix approach: a case study of Sutlej River, Pakistan - Muhammad Shahid Iqbal; Majedul Islam; Mujtaba Hassan; Hazrat Bilal; Izaz Ali Shah; Tzoraki Ourania (Environmental Science and Pollution Research, 2022)

Appraisal and risk assessment of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and organochlorine pesticides (OCPs) in wastewater irrigated area - Yusra Mahfooz; Abdullah Yasar; Liu Guijian; Qamer Ul Islam; Rizwan Rasheed; Muhammad Afzaal; Hifza Butt; Urooj Naeem (Arabian Journal of Geosciences, 2022)

Nutritional Profiling of Wild (Pangasius pangasius) and Farmed (Pangasius hypophthalmus) Pangasius Catfish with Implications to Human Health - Suprakash Chakma; Md. Arifur Rahman; Muhammad A. B. Siddik; Md. Sazedul Hoque; SM Majharul Islam; Ioannis N. Vatsos (Fishes, 2022)
This study analyzed and compared the nutritional profiles of wild (Pangasius pangasius) and farmed (Pangasius hypophthalmus) pangasius catfish collected from the various sources of river and culture ponds in Bangladesh. The results indicated that the wild pangasius catfish had a significantly (p

Abundance, characteristics, and spatial–temporal distribution of microplastics in sea salts along the Cox’s Bazar coastal area, Bangladesh - Muhammad Saiful Islam; Md. Rashed Hasan; Zahidul Islam (Environmental Science and Pollution Research, 2022)

Nutritional Value of Dry Fish in Bangladesh and Its Potential Contribution to Addressing Malnutrition: A Narrative Review - Md. Hasan Al Banna; Abdullah Al Zaber; Nahidur Rahman; Md Abrar Mozahid Siddique; Muhammad Abu Bakr Siddique; John Elvis Hagan; M. A. Rifat; Christiana Naa Atsreh Nsiah-Asamoah; Abdul-Aziz Seidu; Bright Opoku Ahinkorah; Md Shafiqul Islam Khan (Fishes, 2022)
Understanding the linkage between the nutrient composition of foods and individuals’ recommended nutrient intake is important to address malnutrition. Despite it being a traditional and popular food item in Bangladesh, the nutrient composition of dry fish has not been reviewed yet. This study used a narrative review to assess the nutrient composition of dry fish and estimated its potential contribution to addressing some common nutritional deficiencies among children and pregnant and lactating women in Bangladesh. Records were collected from different databases, including the Web of Science, Google Scholar, PubMed, ScienceDirect, Banglajol, and ResearchGate. Data were extracted from 48 articles containing 1128 entries regarding nutrient composition. Most of the nutrient analyses estimated the proximate composition, whereas vitamin, mineral, amino acid, and fatty acid compositions were scarce in the literature. We found that dry fish has high protein and mineral content and could contribute highly to meeting the recommended nutrient intake of protein, iron, zinc, and calcium for children and pregnant and lactating women. The summarized nutrient composition data could be useful for further research to observe how dry fish could be best utilized to address malnutrition in Bangladesh. This narrative review recommends that further nutrient analysis, with emphasis on vitamin, mineral, and fatty acid compositions.

How do multiple kernel functions in machine learning algorithms improve precision in flood probability mapping? - Muhammad Aslam Baig; Donghong Xiong; Mahfuzur Rahman; Md. Monirul Islam; Ahmed Elbeltagi; Belayneh Yigez; Dil Kumar Rai; Muhammad Tayab; Ashraf Dewan (Natural Hazards, 2022)

A comprehensive review of heavy metal pollution in the coastal areas of Bangladesh: abundance, bioaccumulation, health implications, and challenges - Md.Refat Jahan Rakib; Md. Asrafur Rahman; Amarachi Paschaline Onyena; Rakesh Kumar; Aniruddha Sarker; M. Belal Hossain; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Mostafizur Rahman; Yeasmin Nahar Jolly; Abubakr M. Idris; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2022)

Contribution of structural and functional adaptations of hyper-accumulator Suaeda vera Forssk. ex J.F. Gmel. for adaptability across salinity gradients in hot desert - Nargis Naz; Sana Fatima; Mansoor Hameed; Muhammad Ashraf; Muhammad Sajid Aqeel Ahmad; Farooq Ahmad; Syed Mohsan Raza Shah; Faakeha Islam; Iftikhar Ahmad; Farial Ejaz; Mehwish Naseer (Environmental Science and Pollution Research, 2022)

Potential of Fish Scale Biochar Nanocomposite with ZnO for Effective Sequestration of Cr (VI) from Water: Modeling and Kinetics - Azhar Ul Islam; Muhammad Mohsin Iqbal; Muhammad Imran; Muhammad Adnan Tariq; Muhammad Nadeem; Muhammad Qasim Kakar; Muhammad Nawaz; Muhammad Amjad; Saeed Ahmad Qaisrani; Muhammad Rizwan; Shafaqat Ali (International Journal of Environmental Research, 2022)

Rep-PCR Analyses Reveal Genetic Variation of Ralstonia solanacearum Causing Wilt of Solanaceaous Vegetables in Bangladesh - Md. Mosharraf Hossain; Md. Mostafa Masud; Muhammad Iqbal Hossain; Mohammad Mahbubul Haque; Mohammad Sharif Uddin; Md. Zahangir Alam; Md. Rashidul Islam (Current Microbiology, 2022)

Resveratrol and neuroprotection: an insight into prospective therapeutic approaches against Alzheimer’s disease from bench to bedside - Fahadul Islam; Mohamed H. Nafady; Md. Rezaul Islam; Susmita Saha; Salma Rashid; Aklima Akter; Md. Harun- Or-Rashid; Muhammad Furqan Akhtar; Asma Perveen; Ghulam Md. Ashraf; Md. Habibur Rahman; Sherouk Hussein Sweilam (Molecular Neurobiology, 2022)

Correction to: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Multifaceted role of natural sources for COVID-19 pandemic as marine drugs - Md. Mominur Rahman; Md. Rezaul Islam; Sheikh Shohag; Md. Emon Hossain; Muddaser Shah; Shakil khan shuvo; Hosneara Khan; Md. Arifur Rahman Chowdhury; Israt Jahan Bulbul; Md. Sarowar Hossain; Sharifa Sultana; Muniruddin Ahmed; et al. (Environmental Science and Pollution Research, 2022)

A pilot study for enhanced transformation of a metabolite 3,5-dichloroaniline derived from dicarboximide fungicides through immobilized laccase mediator system - Aniruddha Sarker; Tofazzal Islam; Muhammad Bilal; Jang-Eok Kim (Environmental Science and Pollution Research, 2022)

Bionomics and management of aphid, Brevicoryne brassicae (Homoptera: Aphididae) on canola (Brassica napus) using Chrysoperla carnea - Muhammad Mamoon-ur-Rashid; Syed Wajhi-ul-Abbas; Habib Ali; Hussan Ara Beghum; Waqar Islam; Madiha Zaynab; Mubasher Hussain; Obaid Ullah Sayal; Habib ur Rehman; Asif Latif (International Journal of Tropical Insect Science, 2022)

Fruit rot of cowa (Garcinia cowa): a new disease record from Bangladesh - Muhammad Ziaur Rahman; Mohammad Mazharul Karim; Md Muzahid E. Rahman; Raziuddin; Md Rasedul Islam; Md. Mostafizur Rahman Talukder; Md Shamim Akhter; Firoza Khatun (Indian Phytopathology, 2022)

Advanced research tools for fungal diversity and its impact on forest ecosystem - Muhammad Adnan; Waqar Islam; Liu Gang; Han Y. H. Chen (Environmental Science and Pollution Research, 2022)

Therapeutic potential of herbal medicine for the management of hyperlipidemia: latest updates - Abdur Rauf; Muhammad Akram; Hina Anwar; Muhammad Daniyal; Naveed Munir; Sami Bawazeer; Saud Bawazeer; Maksim Rebezov; Abdelhakim Bouyahya; Mohammad Ali Shariati; Muthu Thiruvengadam; Orynzhamal Sarsembenova; et al. (Environmental Science and Pollution Research, 2022)

Solar photo-oxidation of recalcitrant industrial wastewater: a review - Ahmed Tawfik; Mohamed Gar Alalm; Hanem M. Awad; Muhammad Islam; Muhammad Abdul Qyyum; Ala’a H. Al-Muhtaseb; Ahmed I. Osman; Moonyong Lee (Environmental Chemistry Letters, 2022)
Conventional methods to clean wastewater actually lead to incomplete treatments, calling for advanced technologies to degrade recalcitrant pollutants. Herein we review solar photo-oxidation to degrade the recalcitrant contaminants in industrial wastewater, with focus on photocatalysts, reactor design and the photo-Fenton process. We discuss limitations due to low visible-light absorption, catalyst collection and reusability, and production of toxic by-products. Photodegradation of refractory organics by solar light is controlled by pH, photocatalyst composition and bandgap, pollutant properties and concentration, irradiation type and intensity, catalyst loading, and the water matrix.

Exploring the potential of Eocene carbonates through petrographic, geochemical, and geotechnical analyses for their utilization as aggregates for engineering structures - Abdul Rahim Asif; Ihtisham Islam; Waqas Ahmed; Muhammad Sajid; Adnan Qadir; Allah Ditta (Arabian Journal of Geosciences, 2022)

Assessment of heavy metals from pangasius and tilapia aquaculture in Bangladesh and human consumption risk - Md. Emranul Ahsan; Seikh Razibul Islam; Muhammad Abdur Razzak; Md. Lokman Ali; Mohammad Mahfujul Haque (Aquaculture International, 2022)

Renewable and non-renewable energy consumption driven sustainable development in ASEAN countries: do financial development and institutional quality matter? - Md.Monirul Islam; Md.Idris Ali; Brian Ceh; Sanjeet Singh; Muhammad Kamran Khan; Vishal Dagar (Environmental Science and Pollution Research, 2022)

Sub-lethal effects of organophosphates and synthetic pyrethroid insecticides on muscle tissue transaminases of Oreochromis niloticus in vivo - Muhammad Amin; Masarrat Yousuf; Naveed Ahmad; Mohammad Attaullah; Muhammad Ikram; Attia A. Abou Zaid; Clement Ameh Yaro; Eida M. Alshammari; Yaser S. Binnaser; Gaber El-Saber Batiha; Islam Dad Buneri (Toxicological Research, 2022)

Erratum to: Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
The article “Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan”, written by ISLAM Muhammad, RAZZAQ Abdul, ZUBAIR Muhammad, HASSAN Sawsan, AHMAD Sarfraz, GUL Shamim, RISCHKOWSKY Barbara and LOUHAICHI Mounir, was originally published electronically on the publisher’s internet portal (currently SpringerLink) on 27 December 2021 without open access. With the author’s decision to opt for open choice the copyright of the article changed in 02/2022 to © The Author(s) 2022. This article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons license, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons license, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons license and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/ . The original article has been corrected.

Physiological impacts on construction workers under extremely hot and humid weather - Ammar Moohialdin; Bambang Trigunarsyah; Muhammad Saiful Islam; Mohsin K. Siddiqui (International Archives of Occupational and Environmental Health, 2022)

Sugarcane cultivar-dependent changes in assemblage of soil rhizosphere fungal communities in subtropical ecosystem - Muhammad Tayyab; Nyumah Fallah; Caifang Zhang; Ziqin Pang; Waqar Islam; Sheng Lin; Wenxiong Lin; Hua Zhang (Environmental Science and Pollution Research, 2022)

Effects of convective available potential energy, temperature and humidity on the variability of thunderstorm frequency over Bangladesh - Md Wahiduzzaman; Md. Arfan Ali; Jing-Jia Luo; Yu Wang; Md. Jalal Uddin; Shamsuddin Shahid; A. R. M. Towfiqul Islam; Sanjit Kumar Mondal; Ubaydur Rahaman Siddiki; Muhammad Bilal; Zhongfeng Qiu; Ramzah Dambul; et al. (Theoretical and Applied Climatology, 2022)

Sarcopenia in pulmonary diseases is associated with elevated sarcoplasmic reticulum stress and myonuclear disorganization - Rizwan Qaisar; Shahjahan Ustrana; Tahir Muhammad; Islam Shah (Histochemistry and Cell Biology, 2022)

Heavy metals contamination and associated health risks in food webs—a review focuses on food safety and environmental sustainability in Bangladesh - Aniruddha Sarker; Jang-Eok Kim; Abu Reza Md. Towfiqul Islam; Muhammad Bilal; Md. Refat Jahan Rakib; Rakhi Nandi; Mohammed M. Rahman; Tofazzal Islam (Environmental Science and Pollution Research, 2022)

Impact of rangeland enclosure and seasonal grazing on protected and unprotected rangelands in Chakwal region, Pakistan - Muhammad Islam; Abdul Razzaq; Muhammad Zubair; Sawsan Hassan; Sarfraz Ahmad; Shamim Gul; Barbara Rischkowsky; Mounir Louhaichi (Journal of Mountain Science, 2022)
Scrub rangelands support livestock grazing and provide ecosystem services to their inhabitants. The present study was conducted in Chakwal, an important tract of the Pothwar Plateau, which sustains herds of small domestic and nomadic ruminants. Urbanization and uncontrolled grazing practices have reduced rangeland productivity and increased soil erosion and resulted in poor land conditions. This study assessed the influence of two years of rangeland protection on aboveground vegetation biomass and the chemical composition of plants and aimed to determine the influence of seasonal grazing on the live-weight gain of small ewes. Using the line intercept method, vegetation data from protected and unprotected plots in 2015 and 2016 were collected at two sites, Dhulli and Begal. Vegetation cover was assessed from images using VegMeasure. Results showed that protected study sites displayed higher vegetation biomass (834 and 690 kg ha -1 ) compared to the unprotected study site (477 and 326 kg ha -1 ) during April and August of both years. In the seasonal grazing trial, the experimental ewes that grazed on protected rangelands showed higher live-weight gain (33–63 g day -1 ) compared to live weight of ewes (17–21 g day -1 ) that grazed on unprotected rangelands during the experimental period of 127 days at both sites. The results suggest that the Chakwal rangeland has tremendous potential to improve vegetation productivity but modern livestock management and seasonal grazing practices are needed to improve carrying capacity and livestock productivity.

QbD Approach towards Robust Design Space for Flutamide/PiperineSelf-Emulsifying Drug Delivery System with Reduced Liver Injury - Mithun Saha; Pallabi Sikder; Aditi Saha; Sharha Shah; Sharmin Sultana; Tushar Emran; Ananna Banik; Zahidul Islam; Muhammad Saiful Islam; Shazid Md. Sharker; Hasan Mahmud Reza (AAPS PharmSciTech, 2022)

Social support, source credibility, social influence, and solar photovoltaic panels purchase intention - Xiaobei Liang; Xiaojuan Hu; Tahir Islam; Muhammad Shujaat Mubarik (Environmental Science and Pollution Research, 2021)

Heavy Metals Accumulation in Dragonflies (Odonata) and Their Habitats in District Swabi, Khyber Pakhtunkhwa, Pakistan: Assessing Dragonfly Bionomics in the Region - Hajra Noor-Ul-Islam; Khurshaid Khan; Syed Ahmed Zia; Muhammad Naeem; Waqas Ahmad Shams (Bulletin of Environmental Contamination and Toxicology, 2021)

Pharmacological evaluation of the gabapentin salicylaldehyde derivative, gabapentsal, against tonic and phasic pain models, inflammation, and pyrexia - Nisar Ahmad; Fazal Subhan; Nazar Ul Islam; Muhammad Shahid; Naseem Ullah; Rahim Ullah; Muhammad Khurram; Muhammad Usman Amin; Shehla Akbar; Ihsan Ullah; Robert D. E. Sewell (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Impact of invasive ant species on native fauna across similar habitats under global environmental changes - Junaid Ali Siddiqui; Bamisope Steve Bamisile; Muhammad Musa Khan; Waqar Islam; Muhammad Hafeez; Imran Bodlah; Yijuan Xu (Environmental Science and Pollution Research, 2021)

Health risk assessment of endocrine disruptor bisphenol A leaching from plastic bottles of milk and soft drinks - Muhammad Umar Farooq; Muhammad Irfan Jalees; Qurat-ul-Ain; Ghulam Hussain; Mehwish Anis; Ummara Islam (Environmental Science and Pollution Research, 2021)

Chromium Exposure Causes Structural Aberrations of Erythrocytes, Gills, Liver, Kidney, and Genetic Damage in Striped Catfish Pangasianodon hypophthalmus - Sajida Akter Suchana; Md Shaker Ahmed; S. M. Majharul Islam; Muhammad Lutfar Rahman; Md Fazle Rohani; Tanzina Ferdusi; A. K. Shakur Ahmmad; Mst Kaniz Fatema; Muhammad Badruzzaman; Md Shahjahan (Biological Trace Element Research, 2021)

Challenges and prospects for a potential allohexaploid Brassica crop - Kangni Zhang; Annaliese S. Mason; Muhammad A. Farooq; Faisal Islam; Daniela Quezada-Martinez; Dandan Hu; Su Yang; Jun Zou; Weijun Zhou (Theoretical and Applied Genetics, 2021)

Impact of globalization, foreign direct investment, and energy consumption on CO2 emissions in Bangladesh: Does institutional quality matter? - Md. Monirul Islam; Muhammad Kamran Khan; Mohammad Tareque; Noor Jehan; Vishal Dagar (Environmental Science and Pollution Research, 2021)

Sugarcane monoculture drives microbial community composition, activity and abundance of agricultural-related microorganisms - Muhammad Tayyab; Ziqi Yang; Caifang Zhang; Waqar Islam; Wenxiong Lin; Hua Zhang (Environmental Science and Pollution Research, 2021)

Sumithion usage in aquaculture: benefit or forfeit? - Md Shahjahan; SM Majharul Islam; Alif Layla Bablee; Muhammad A.B. Siddik; Ravi Fotedar (Reviews in Aquaculture, 2021)
Sumithion is an organophosphate insecticide, extensively used to remove tiger bug from aquaculture ponds prior to the release of fish larvae. Its usage in aquaculture may initially assist in insect eradication; however, the harmful effects of sumithion may surpass the beneficial effects and may be alarming for the farmed fish and other aquatic organisms. This study summarizes the consequential effects of sumithion on the natural productivity in aquaculture ponds, and early development, physiological response, and reproductive functions of the farmed fish. Studies have found that sumithion adversely affects the natural production of phytoplankton, zooplankton and benthos, and reduces the hatching success with increased mortality, and morphological alterations in fish embryos and larvae. Fish haematological and biochemical alterations are also reported to be induced by the exposure to sumithion, as are variety of histopathological alterations and reproductive dysfunctions in exposed fish. Overall, this study is the first comprehensive overview of any insecticide which may advance our understanding of the rational and restricted use of insecticide in aquaculture operations.

COVID-19 transmission, vulnerability, persistence and nanotherapy: a review - Afzal Husain Khan; Vineet Tirth; Manal Fawzy; Alaa El Din Mahmoud; Nadeem A. Khan; Sirajuddin Ahmed; Syed Sadat Ali; Muhammad Akram; Leena Hameed; Saiful Islam; Gotam Das; Sharmili Roy; et al. (Environmental Chemistry Letters, 2021)

Nonlinear postural control paradigm for larger perturbations in the presence of neural delays - Nadia Sultan; Muhammad Najam ul Islam; Asif Mahmood Mughal (Biological Cybernetics, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Employing social vulnerability index to assess household social vulnerability of natural hazards: an evidence from southwest coastal Bangladesh - Anjum Tasnuva; Md. Riad Hossain; Roquia Salam; Abu Reza Md. Towfiqul Islam; Muhammad Mainuddin Patwary; Sobhy M. Ibrahim (Environment, Development and Sustainability, 2021)

Phyto-derivatives: an efficient eco-friendly way to manage Trogoderma granarium (Everts) (Coleoptera: Dermestidae) - Waqar Islam; Ali Noman; Komivi Senyo Akutse; Muhammad Qasim; Habib Ali; Ijaz Haider; Mohamed Hashem; Saad Alamri; Omar Mahmoud al Zoubi; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Correction to: Environmental Integrants Affecting the Spreadability of SARS‑CoV‑2 - Muhammad Torequl Islam (Food and Environmental Virology, 2021)

First Record of Australian Sawcheek Scorpionfish, Brachypterois curvispina, (Actinopterygii: Scorpaeniformes: Scorpaenidae) From the St. Martin Island, Bangladesh - Md. Abu Hanif; Muhammad A. B. Siddik; Md. Aminul Islam; Md. Rajib Sharker (Thalassas: An International Journal of Marine Sciences, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Comparative pathogenicity of four entomopathogenic fungal species against nymphs and adults of citrus red mite on the citrus plantation - Muhammad Qasim; Jiang Ronliang; Waqar Islam; Habib Ali; Khalid Ali Khan; Chandra Kanta Dash; Zakia A. Jamal; Liande Wang (International Journal of Tropical Insect Science, 2021)

Degradation of different pesticides in water by microplasma: the roles of individual radicals and degradation pathways - Muhammad Saiful Islam Khan; Na Ri Lee; Jaehwan Ahn; Ji Young Kim; Jong Hoon Kim; Ki Hyun Kwon; Yun-Ji Kim (Environmental Science and Pollution Research, 2021)

Screening for drought tolerance in wheat genotypes by morphological and SSR markers - Muhammad Shahidul Haque; Nihar Ranjan Saha; Muhammad Tariqul Islam; Muhammad Monirul Islam; Soo-Jeong Kwon; Swapan Kumar Roy; Sun-Hee Woo (Journal of Crop Science and Biotechnology, 2021)

Recent advances, approaches and challenges in targeting pathways for potential COVID-19 vaccines development - Daniela Calina; Chandan Sarkar; Andreea Letitia Arsene; Bahare Salehi; Anca Oana Docea; Milon Mondal; Muhammad Torequl Islam; Alireza Zali; Javad Sharifi-Rad (Immunologic Research, 2020)

Characterization and adsorption capacity of modified 3D porous aerogel from grapefruit peels for removal of oils and organic solvents - Muhammad Imran; Ashraful Islam; Muhammad Umair Farooq; Junpei Ye; Panyue Zhang (Environmental Science and Pollution Research, 2020)

First report of apple mosaic virus in peach in Pakistan - Azhar Ul Islam; Muhammad Wahaj Javed; Muhammad Akram; Javed Rahman; Muhammad Tahir; Muhammad Farooq Hussain Munis; Abu Bakr Umer Farooq (Journal of Plant Pathology, 2020)

The sorbed mechanisms of engineering magnetic biochar composites on arsenic in aqueous solution - Zulqarnain Haider Khan; Minling Gao; Weiwen Qiu; Muhammad Qaswar; Md. Shafiqul Islam; Zhengguo Song (Environmental Science and Pollution Research, 2020)

Environmental Integrants Affecting the Spreadability of SARS-CoV-12 - Muhammad Torequl Islam (Food and Environmental Virology, 2020)

A new biochar from cotton stalks for As (V) removal from aqueous solutions: its improvement with H3PO4 and KOH - Munawar Hussain; Muhammad Imran; Ghulam Abbas; Muhammad Shahid; Muhammad Iqbal; Muhamamd Asif Naeem; Behzad Murtaza; Muhammad Amjad; Noor Samad Shah; Zia Ul Haq Khan; Azhar Ul Islam (Environmental Geochemistry and Health, 2020)

Angiostatic effects of ascorbic acid: current status and future perspectives - Muhammad Torequl Islam (Angiogenesis, 2020)

Chemical profile and biological activities of Sonneratia apetala (Buch.-Ham.) - Muhammad Torequl Islam (Advances in Traditional Medicine, 2020)

Litter decay in rangeland sites with varying history of human disturbance: a study with Hazargangi Chiltan mountain - Imran Khan; Shamim Gul; Sarfraz Ahmad; Gul Bano Rehman; Agha Waqar Yunus; Iram Gul; Imran Ali; Ali Akbar; Muhammad Islam (Journal of Mountain Science, 2020)

Evaluation of the bioenergy potential of invasive Pennisetum purpureum through pyrolysis and thermogravimetric analysis - Md Sumon Reza; Shafi Noor Islam; Shammya Afroze; Muhammad S. Abu Bakar; Rahayu S. Sukri; Saidur Rahman; Abul K. Azad (Energy, Ecology and Environment, 2020)

Pyrrolidine alkaloids and their promises in pharmacotherapy - Muhammad Torequl Islam; Mohammad Suleiman Mubarak (Advances in Traditional Medicine, 2020)

Cytogenotoxicological Effects of the Methanolic Extract of Dysophylla auricularia - Muhammad Torequl Islam; Eunus S. Ali; Shaikh Jamal Uddin; Swati Tripathi; Ana Amélia de Carvalho Melo-Cavalcante; Siddhartha Kumar Mishra (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Antipyretic effect of phytol, possibly via 5KIR-dependent COX-2 inhibition pathway - Muhammad Torequl Islam (Inflammopharmacology, 2019)

Assessment of nematodes in Punjab Urial (Ovis vignei punjabiensis) population in Kalabagh Game Reserve: development of a DNA barcode approach - Amna Arshad Bajwa; Jordan Patrick Cuff; Muhammad Imran; Saher Islam; Riffat Mansha; Kamran Ashraf; Arman Khan; Muhammad Imran Rashid; Muhammad Yasir Zahoor; Waseem Ahmad Khan; Habib Ur Rehman; Asif Nadeem; et al. (European Journal of Wildlife Research, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Role of phosphorous mining in mobilization and bioaccessibility of heavy metals in soil-plant system: Abbottabad, Pakistan - Afshan; Sajjad Ahmad; Muhammad Imran; Rab Nawaz; Muhammad Arshad; Muhammad Ejaz Ul Islam Dar; Muhammad Hussnain Siddque; Muhammad Nadeem; Liaqat Ali (Arabian Journal of Geosciences, 2019)

Synergistic effects of chromium and copper on photosynthetic inhibition, subcellular distribution, and related gene expression in Brassica napus cultivars - Lan Li; Meijuan Long; Faisal Islam; Muhammad A. Farooq; Jian Wang; Theodore M. Mwamba; Jianyao Shou; Weijun Zhou (Environmental Science and Pollution Research, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Molecular epidemiology of bovine anaplasmosis in Khyber Pakhtunkhwa, Pakistan - Shahid Hussain Farooqi; Muhammad Ijaz; Muhammad Imran Rashid; H. Nabi; S. Islam; Amjad Islam Aqib; Kashif Hussain; Amjad Khan; Syeda Nayab Batool Rizvi; Shakeel Mahmood; Khalid Mehmood; Hui Zhang (Tropical Animal Health and Production, 2018)

Storm protection service of the Sundarbans mangrove forest, Bangladesh - Md. Ali Akber; Muhammad Mainuddin Patwary; Md. Atikul Islam; Mohammad Rezaur Rahman (Natural Hazards, 2018)

Complete genome sequences of three novel cycloviruses identified in a dragonfly (Odonata: Anisoptera) from China - Saif Ul Islam; Wenzhong Lin; Ran Wu; Chen Lin; Waqar Islam; Muhammad Arif; Zhenguo Du; Zujian Wu (Archives of Virology, 2018)

Sugar beet extract acts as a natural bio-stimulant for physio-biochemical attributes in water stressed wheat (Triticum aestivum L.) - Ali Noman; Qasim Ali; Jazia Naseem; M. Tariq Javed; Hina Kanwal; Waqar Islam; Muhammad Aqeel; Noreen Khalid; Sara Zafar; Muhammad Tayyeb; Naeem Iqbal; Mahmooda Buriro; et al. (Acta Physiologiae Plantarum, 2018)

Salinity reduces 2,4-D efficacy in Echinochloa crusgalli by affecting redox balance, nutrient acquisition, and hormonal regulation - Faisal Islam; Yuan Xie; Muhammad A. Farooq; Jian Wang; Chong Yang; Rafaqat A. Gill; Jinwen Zhu; Weijun Zhou (Protoplasma, 2018)

Impact of grazing on soil, vegetation and ewe production performances in a semi-arid rangeland - Muhammad Islam; Abdul Razzaq; Shamim Gul; Sarfraz Ahmad; Taj Muhammad; Sawsan Hassan; Barbara Rischkowsky; M. N. M. Ibrahim; Mounir Louhaichi (Journal of Mountain Science, 2018)

Screening for gene–environment (G×E) interaction using omics data from exposed individuals: an application to gene-arsenic interaction - Maria Argos; Lin Tong; Shantanu Roy; Mekala Sabarinathan; Alauddin Ahmed; Md. Tariqul Islam; Tariqul Islam; Muhammad Rakibuz-Zaman; Golam Sarwar; Hasan Shahriar; Mahfuzar Rahman; Md. Yunus; et al. (Mammalian Genome, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Proteomic approach to address low seed germination in Cyclobalnopsis gilva - Madiha Zaynab; Sonia Kanwal; Muhammad Furqan; Waqar Islam; Ali Noman; Ghulam Muhammad Ali; Nazia Rehman; Sara Zafar; Kalsoom Sughra; Muhammad Jahanzab (Biotechnology Letters, 2017)

A long-term trend in precipitation of different spatial regions of Bangladesh and its teleconnections with El Niño/Southern Oscillation and Indian Ocean Dipole - Md. Kawser Ahmed; Mohammad Samsul Alam; Abu Hena Muhammad Yousuf; Md. Monirul Islam (Theoretical and Applied Climatology, 2017)

Occupational and life-style factors-acquired mutagenicity in agric-workers of northeastern Brazil - Tatiana Vieira Souza Chaves; Muhammad Torequl Islam; Manoel Odoríco de Moraes; Marcus Vinícius Oliveira Barros de Alencar; Débora Cássia Vieira Gomes; Rodrigo Mendes de Carvalho; Sharbel Weider Maluf; Fabrício Pires de Moura do Amaral; Márcia Fernanda Correia Jardim Paz; Gilberto Santos Cerqueira; Hercília Maria Lins Rolim; João Marcelo de Castro e Sousa; et al. (Environmental Science and Pollution Research, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)

Current advancements of magnetic nanoparticles in adsorption and degradation of organic pollutants - Mazhar Ul-Islam; Muhammad Wajid Ullah; Shaukat Khan; Shehrish Manan; Waleed Ahmad Khattak; Wasi Ahmad; Nasrullah Shah; Joong Kon Park (Environmental Science and Pollution Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Subcellular distribution, modulation of antioxidant and stress-related genes response to arsenic in Brassica napus L. - Muhammad A. Farooq; Rafaqat A. Gill; Basharat Ali; Jian Wang; Faisal Islam; Shafaqat Ali; Weijun Zhou (Ecotoxicology, 2016)

Environment and air pollution like gun and bullet for low-income countries: war for better health and wealth - Xiang Zou; Muhammad Azam; Talat Islam; Khalid Zaman (Environmental Science and Pollution Research, 2016)

Novel Controlled Release Polymer-Lipid Formulations Processed by Hot Melt Extrusion - Mohammed Maniruzzaman; Muhammad T. Islam; Sheelagh Halsey; Devyani Amin; Dennis Douroumis (AAPS PharmSciTech, 2016)

Copper-resistant bacteria reduces oxidative stress and uptake of copper in lentil plants: potential for bacterial bioremediation - Faisal Islam; Tahira Yasmeen; Qasim Ali; Muhammad Mubin; Shafaqat Ali; Muhammad Saleem Arif; Sabir Hussain; Muhammad Riaz; Farhat Abbas (Environmental Science and Pollution Research, 2016)

Consumer purchase intention towards environmentally friendly vehicles: an empirical investigation in Kuala Lumpur, Malaysia - Rafia Afroz; Muhammad Mehedi Masud; Rulia Akhtar; Md. Ashraful Islam; Jarita Bt Duasa (Environmental Science and Pollution Research, 2015)

Priming-induced antioxidative responses in two wheat cultivars under saline stress - Faisal Islam; Tahira Yasmeen; Shafaqat Ali; Basharat Ali; Muhammad A. Farooq; Rafaqat A. Gill (Acta Physiologiae Plantarum, 2015)

Development of sustained-release formulations processed by hot-melt extrusion by using a quality-by-design approach - Muhammad T. Islam; Mohammed Maniruzzaman; Sheelagh A. Halsey; Babur Z. Chowdhry; Dennis Douroumis (Drug Delivery and Translational Research, 2014)

Integrated effects of organic, inorganic and biological amendments on methane emission, soil quality and rice productivity in irrigated paddy ecosystem of Bangladesh: field study of two consecutive rice growing seasons - Muhammad Aslam Ali; M. A. Sattar; M. Nazmul Islam; K. Inubushi (Plant and Soil, 2014)

Synthetically modified bioisosteres of salicyl alcohol and their gastroulcerogenic assessment versus aspirin: biochemical and histological correlates - Gowhar Ali; Fazal Subhan; Nazar Ul Islam; Nasir Ullah; Robert D. E. Sewell; Muhammad Shahid; Ikhtiar Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Expression line approach to recombinant human epidermal growth factor into the yeast, Pichia pastoris from Huh-7 cell line - Mohsin Ahmad Khan; Faidad Khan; Nadeem Ahmad; Muhammad Islam Khan; Ahmad Usman Zafar; Tayyab Husnain (Molecular Biology Reports, 2014)

A Putative Leucine-Rich Repeat Receptor-Like Kinase of Jute Involved in Stress Response - Md. Maksudul Alam; Sazia Sharmin; Zinnatun Nabi; Shakhinur Islam Mondal; Md. Shahidul Islam; Sarmah Bin Nayeem; Muhammad Shoyaib; Haseena Khan (Plant Molecular Biology Reporter, 2010)

Future change in the frequency of warm and cold spells over Pakistan simulated by the PRECIS regional climate model - Siraj ul Islam; Nadia Rehman; Muhammad Munir Sheikh (Climatic Change, 2009)

Urban and peri-urban aquaculture as an immediate source of food fish: Perspectives of Dhaka City, Bangladesh - MD. Shahidul Islam; Muhammad Tanvir Hossain Chowdhury; MD. Mokhlesur Rahman; MD. Anwar Hossain (Urban Ecosystems, 2004)

Response of three wheat genotypes grown under saline medium to low/high potassium levels - M. U. Shirazi; B. Khanzada; Muhammad Ali; Ejaz ul Islam; S. M. Mujtaba; R Ansari; S. M. Alam; M. A. Khan; Mukhtiar Ali (Acta Physiologiae Plantarum, 2002)